Regulating the d-band center of Ru/CoMoO4 ternary heterostructure by interface engineering for accelerated hydrogen adsorption kinetics - Miao Ma; Min Yang; Cai-Yue Zhang; Hai-Yi Sun; Rong-Jing Su; Xiao-Rui Yue; Chen-Xi Li; Yong-Ming Chai; Bin Dong (Fuel, 2026)

Role of glutamine in promoting the proliferation and chondrogenic differentiation of ATDC5 cells: based on transcriptomic analysis - Rui-hao Zhang; Wen-huan Yuan; Ze-long Wang; Qi-rui Yang; Yi Sun; Quan-nian Shao; Wen-ji Wang; Jing Wang (Molecular Biology Reports, 2026)

Insulin-like peptide 3 facilitates sheep oocytes in vitro maturation and subsequent early embryo development - Qi Yang; Rui-Feng Zhang; Zhao-Yu Jiang; Dui Sun; Rui-Hao Tang; Xiao-Yi Zhang; Yi-Tong Li; Wen-Ying Li; Ao Liu; Chun-Lan Zhang; Zhi-Wen Jia; Meng-Lei Feng; et al. (Theriogenology, 2026)

Spatiotemporally energy-managed phase-change evaporators for continuous solar desalination - Qian Chen; Xingdong Qiu; Rui Yang; Jinchi Li; Jun Xia; Hongbing Wang; Lihong Zhou; Yi Lu; Size Zheng; Mingming Zheng; Xiaoke Li (Chemical Engineering Journal, 2026)

Enhancing resistance against white spot syndrome virus in Litopenaeus vannamei via recombinant Lactobacillus acidophilus through modulation of gut microbiota function - Hang Zhang; Wei Liu; Yi-Ning Cui; Pei-Min He; Ji-shun Yang; Rui Jia (Aquaculture, 2026)

Differential regulation of exercise fatigue by Spirulina peptides: energy metabolism and antioxidant defense mechanisms mediated in a comparative swimming model - Tao Ding; Zhaoxin Li; Rui Duan; Junjie Zhang; Lihong Xing; Xiaojie Sun; Fang Zhang; Qingyan Wang; Shuo Qie; Yi Yang; Cuiping Song (Food Chemistry, 2026)

Yield advantage in wide strip intercropping: Border-row effects and adding a third crop in double relay intercropping - Hao Yang; Huai-Ying Ma; Yi-Wen Zhao; Jiu-Dong Zhang; Gui-Zong Zhang; Jia-Kang Lu; Ya-Xian Huang; Xing-Guo Bao; Rui-Peng Yu; Wopke van der Werf; Long Li (Field Crops Research, 2026)

Longitudinal association between metal mixture exposure and non-alcoholic fatty liver disease: A prospective cohort study based on generative adversarial networks - Jiaming Fu; Jinhao Jia; Honghui Li; Guojie Qiao; Zeyang Bai; Limeng Xiong; Yuhan Zhang; Xiaozhe Geng; Hongju Duan; Yuxi Wang; Chunqing Gao; Xiaoyu Li; et al. (Environmental Pollution, 2026)

A biomimetic mineralized injectable hydrogel enables spatiotemporal dual-drug delivery for colorectal cancer therapy - Jing-Yu Feng; Rui Zhang; Jing-Ling Yang; Rui Lu; Kiran Thakur; Fei Hu; Yi-Long Ma; Jian-Guo Zhang; Zhao-Jun Wei (Chemical Engineering Journal, 2026)

A lyophilized RPA–CRISPR/Cas13d one-pot platform for rapid detection of porcine circovirus type 3 - Li-Na Shao; Zheng-Luo; Bao-Ling Liu; Tong-Xu; Yuan-Meng Wang; Jia-Qi Duan; Lei-Zhao; You-You Li; Yang-Ming Dai; Qin-Rui Jia; Le-Yi Zhang; Ling-Zhu; et al. (Analytica Chimica Acta, 2026)

Harnessing a MMP-sensitive fluorescent probe for in-situ and reversible monitoring MMP alteration in dual color based on aggregation/monomer mechanism - Mengmeng Wei; Yuxuan Zhang; Wuyou Qiang; Jiawei Liu; Yi Qian; Jing Xu; Xiaoyan Tang; Jiaojiao Liu; Shenqiang Wang; Tingwang Jiang; Xifeng Yang; Xuekun Hong; et al. (Analytica Chimica Acta, 2026)

Differential effects of alcohol-derived serum metabolites and direct ethanol exposure on mouse preantral follicle development - Meng-Ting Cao; Yang Shi; Chun Li; Yi-Lin Fan; Zhu-Rong Hu; Le-Ning Dang; Xue-Rui He; Wei-Qiang Luo; Jing-Jing Li; Xing-Rong Yan (Chemico-Biological Interactions, 2026)

A parallel electrical impedance tomography system for tissue-resolved imaging of relative stem conductivity dynamics in sunflower under PEG-induced stress - Liu-Deng Zhang; Ao-Wen Wang; Bing-Zhou Chen; Yang Xiang; Yu-Bin Lin; Chang Chen; Huan-Rui Ge; Ke-Lei Xia; Li-Feng Fan; Lan Huang; Zhong-Yi Wang (Biosystems Engineering, 2026)

Synergistic integration of in situ generated Fe-S species and organohalide-respiring bacteria for complete dechlorination of carbon tetrachloride in groundwater - Boyu Jia; Rui Shen; Zhongdan Li; Yijun Mo; Yi Yang; Shanquan Wang (Water Research, 2026)

Corrigendum to “TBBPA induced hepatocyte ferroptosis by PCBP1-mediated ferritinophagy” [J Hazard Mater 494 (2025) 138515] - Rui-Qi Liu; Yu-Tong Wu; Yue Cheng; Yuan-Hang Chang; Muhammad Asmat Ullah Saleem; Zi-Yan Hu; Shang-Jia Yang; Xue-Qi Wang; Yi-Jia Song; Xin-Yue Mao; Jing Zheng; Yi-Bo Wang; et al. (Journal of Hazardous Materials, 2026)

How phosphorus enrichment regulates the microbial community resistance and multifunctions tolerance to drying–rewetting cycles in paddy fields: the critical role of stoichiometry - Jiaying Wang; Yi Xu; Tinghong Fu; Guoxiang You; Rui Wang; Tianyun Li; Zewei Jiang; Shihong Yang (Journal of Environmental Management, 2026)

Nanoconfinement-enhanced cerium@carbon nanotubes composites for adsorption of fluoride - Erming Ouyang; Guangzhe Han; Yi Zhang; Wei Song; Hongwei Yang; Rui Zhao (Environmental Research, 2026)

Quercetin restores oocyte maturation and embryo development in DEHP-exposed mice via mitochondrial protection and apoptosis inhibition - Dui Sun; Qi Yang; Zhi-Hui Gong; Meng-Lei Feng; Zhi-Wen Jia; Bin-Shuo Yang; Zhao-Yu Jiang; Chun-Ru Song; Fang-Rui Xue; Xiao-Jie Zhang; Hao-Yang Zhang; Chun-Lan Zhang; et al. (Chemico-Biological Interactions, 2026)

Effect of the thickness of overlying soil on the location of trailing edge cracks in soil–bedrock landslides induced by water softening - Yun-kang Rao; Jia-xin Chang; Hai-ying Fu; Tao Yang; Huai-lin Chen; Zhe Zhang; Yi Yang; Rui Huang (Bulletin of Engineering Geology and the Environment, 2026)

Kit Ligand enhances in vitro oocyte maturation and early embryonic development in sheep - Qi Yang; Dui Sun; Zhao-Yu Jiang; Rui-Hao Tang; Rui-Feng Zhang; Xiao-Yi Zhang; Wen-Ying Li; Yi-Tong Li; Ao Liu; Chun-Lan Zhang; Zhi-Wen Jia; Meng-Lei Feng; et al. (Animal Reproduction Science, 2026)

Prediction of antibiotic resistance genes and resistance mechanisms of Pseudomonas syringae pv. actinidiae strain L211 based on whole-genome sequencing - Rui Yang; Dan-ni Chen; Shuai Yang; Lang-bo Yi; Qing-zhong Peng (Journal of Plant Pathology, 2026)

Cascade of candidate spin liquids in a bilayer triangular-lattice antiferromagnet Rb2Co2(SeO3)3 - Xiaoyu Xu; Yunlong Wang; Xuejuan Gui; Jun Luo; Guijing Duan; Ke Shi; Zhaosheng Wang; Shuo Li; Huifen Ren; Chuanying Xi; Langsheng Ling; Zhanlong Wu; et al. (Science Bulletin, 2026)

Inhalable HUCMSC-Lipo biomimetic formulation inhibits fibroblast activation in mouse and non-human primate pulmonary fibrosis models - Fangyu Zhao; Yige Sun; Haoran Wang; Dayong Hou; Rui Zhang; Wenjing Xia; Yongchen Zhang; Luyao Li; Xueqi Zhao; Kaiqi Wang; Wenwen Pan; Jiannan Wang; et al. (Science Bulletin, 2026)

Unraveling the adverse outcome pathways of metabolic dysfunction-associated steatotic liver disease triggered by environmental mixtures via biological knowledge-driven machine learning - Jiaming Fu; Guojie Qiao; Kerong Ma; Jinhao Jia; Honghui Li; Zeyang Bai; Limeng Xiong; Yuhan Zhang; Xiaozhe Geng; Hongju Duan; Yuxi Wang; Chunqing Gao; et al. (Journal of Hazardous Materials, 2026)

Co-fermentation of Ampelopsis grossedentata with Camellia sinensis reduces bitterness, enhances sweet aroma, and generates novel bioactive theaflavin analogues - Si-Rui Li; Zi Yang; Na Song; Jia-Yi Li; Yu-Xing Zhang; Hao Li; Peng Zhang; Yu-Lan Song; Yu Sun; Kun Qian; Da-Wei Zhang; Guan-Hu Bao (Food Chemistry, 2026)

Phase-change-gated nanocapsules synchronize fungicide release and plant transport for wheat crown-rot control - Xiquan Ding; Yu Fang; Zheng Zhang; Dongyin Yi; Ze Lv; Yang Gao; Xinyu Guo; Yucheng Gu; Hongyan Zhang; Xuemin Wu; Rui Zhao; Yong Xu (Chemical Engineering Journal, 2026)

Eccentric coaxial wet-spun magnetic composite actuators with decoupled magneto-pneumatic shape-morphing for biomedical applications - Ping-an Yang; Yixuan Han; Chunyan Mo; Mengjie Shou; Rui Li; Yi Lu; Decheng Wu; Qiao Chen; Zhiwei Huang (Chemical Engineering Journal, 2026)

Analysis of Arbuscular Mycorrhizal Fungal Community in Soil of Sugarcane at Different Tillage Depths - Qun-Qing Huang; Sheng Wang; Ying-Jie Nong; Kai-Mao Zhong; Yi-Cheng Su; Xiao-Juan Qin; Jin-Lian Zhang; Yi-Hao Kang; Ting-Su Chen; Shi-Yuan Zeng; Xi-Chao Deng; Ming-Guo Jiang; et al. (Sugar Tech, 2026)

Plastisphere-driven pollutant enrichment and harmful bacteria proliferation: Emerging ecological risks to Danjiangkou reservoir's water security - Tao He; Zhi-Min Xu; Le-Yi Cheng; Yi-Cai Zhang; Shuang Wang; Xiao-Yan Zhang; Xi Yang; Yu-Ting Hou; Si-Yi Wang; Xin-Yue Hu; Xin-Rui Zhou; Yong-Hong Ma; et al. (Marine Pollution Bulletin, 2026)

Unveiling the participation of microbiomes in the trait formation of economically important Pyropia haitanensis varieties - Yi Liu; Jingyi Wang; Qijun Luo; Juanjuan Chen; Rui Yang; Peng Zhang; Tiegan Wang; Huifeng Cai; Haimin Chen (Aquaculture, 2026)

From Lab to Farm: A Low‐Cost Naked‐Eye On‐Site Detecting Platform for Cynoglossus semilaevis Parvovirus Based on Magnetic Beads Adsorption and LAMP ‐ HNB - Shu‐Xia Xue; Si‐Yu Yang; Meng‐Han Xu; Xin‐Rui Liu; Ye‐Xuan Liu; Zi‐Tong Li; Yi‐Xuan Li; Jia‐Ru Hu; Li‐Xian Huang; Xin‐Yi Zhang; Chang Lu; Yu‐Ru Liu; et al. (Journal of Fish Diseases, 2026)
Cynoglossus semilaevis parvovirus (CsPV) is an important pathogen that poses a serious threat to the aquaculture industry. In the absence of vaccines and effective therapeutic drugs, early and sensitive detection of the pathogen is the key measure to prevent and control the outbreaks and epidemics of viral diseases. Currently, the existing detection methods for CsPV are expensive and rely on specialized operations, limiting the application of on‐site detection. There is an urgent need for a low‐cost, user‐friendly detecting platform to prevent fish viral diseases. In this study, we confirmed skin mucus as a target tissue for non‐lethal sampling, established a simple proteinase K digestion, 2% CTAB lysis and silica‐hydroxylated magnetic beads adsorption method for extracting viral genomic DNA from skin mucus and developed a visual one‐pot loop‐mediated isothermal amplification (LAMP) detection method with a sensitivity of 4.69 × 10 1 copies/μL. Validation of the detection platform using clinical samples showed 97% sensitivity and 100% specificity. The cost of reagents for per sample was reduced from 16.6 CNY to 6.2 CNY. The low‐cost naked‐eye on‐site detection platform provides technical support for resource‐limited aquaculture farms to prevent and control emerging viral diseases in Chinese tongue sole.

Organic acids in four representative fermented alcoholic beverages: absorption, metabolic fate, and molecular mechanisms of health benefits - Xiaolu Tian; Rui Zhang; Haijue Zhang; Yi Liang; Yunxiang Ma; Zixuan Yang; Fuliang Han (Critical Reviews in Food Science and Nutrition, 2026)

How to make big data accessible to plant biologists and beyond: Ten years of lessons from TBtools - Junting Feng; Chengjie Chen; Ya Wu; Longjiang Fan; Zhang Zhang; Ming Chen; Haibao Tang; Guangchuang Yu; Jian Ren; Jingchu Luo; Yi Liao; Aiping Luan; et al. (Molecular Plant, 2026)

Differential analysis of lipid profiles in natural Calculus Bovis and Bovis Calculus Sativus by UHPLC-MS/MS - Qiang Mao; Huan Zhong; Wan-Li Liang; Jin Dai; Rui-Ting Huang; Yi-Di Wang; Di-Yang Sun; Kai Tang; Long-Fei Xia; Hai-Biao Gong; Yi-Fang Li; Wan-Yang Sun; et al. (Journal of Natural Medicines, 2026)

Short-term hot spring balneotherapy ameliorates sleep disorders: wrist-worn wearable-assessed sleep improvement associated with neuroimmune, tryptophan metabolic and gut microbiome alterations - Xiao Zhang; Yue Zou; Xiao-qin He; Yi-hang Xu; Hong-xia Li; Fen Yang; Bao-chao Zhang; Lin-xuan Liao; Meng-xi Cao; Rui-xue Wang; Si-fan Hao; Meng-meng Wang; et al. (International Journal of Biometeorology, 2026)

SYVN1-provoked RASA1 ubiquitination promotes pulmonary inflammation in chronic obstructive pulmonary disease - Ju-Hong Wu; Yi-Cheng Ma; Yu-Qi Wang; Hai-Long Miao; Meng-Xue Liu; Dong-Xu Hua; Min-Min Tang; Tian-Rui Sui; Zhi-Yong Wu; Yu Wang; Jin Yang; Hui Zhao; et al. (Inflammation Research, 2026)

Domestic and exotic freshwater fish communities of different water systems under anthropogenic pressures: Diversity patterns, environmental drivers and ecological interactions - Peixuan Wang; Nan Yang; Xiaodong Hu; Lihua Niu; Jixiong Xu; Rui Huang; Li Lin; Yi Li (Journal of Environmental Sciences, 2026)

Germination-tunable structural remodeling of LAB-fermented soymilk gels: Unraveling gastrointestinal digestive fate and bioactive peptide release - Yaqiong Wang; Yi Wang; Zhijie Yao; Xin Rui; Pei Wang; Chong Xie; Runqiang Yang (Food Chemistry, 2026)

Rhizosphere microbial carbon utilization stimulates soil phosphorus fraction transformation in response to maize (Zea mays L.) and soybean (Glycine max.) interspecific interactions - Ruixue Wang; Lizhen Su; Dingjin Li; Zikun Yang; Rui Feng; Yi Zheng; Li Tang (Plant and Soil, 2026)

Quantitative source apportionment of soil geochemical elements in a typical mountain-plain transition zone, northern China: the combined influence of geological background and anthropogenic activities - Huan Li; Yi-Xuan Zhang; Yang Yao; Qin-Rui Zhang; Bo Zhang; Yong-Wei Zhao; Bing Han; Guo-Li Yuan (Environmental Geochemistry and Health, 2026)

Development and validation of a Mn/MOF-808 based colorimetric platform for rapid and reliable on-site monitoring of iodide in marine environments - Yi-Ting Chen; Xiao-Jun Dai; Xi- Qing Xu; Pei Liu; Wen-Ge Zhang; Wen-Rui Zhang; Shu-Xuan Li; Peng Wang; Chun-Hui Gong; Yi Yang (Analytica Chimica Acta, 2026)

Muscone Exerts Rapid Antidepressant Effects Through Modulating Glutamatergic Neural Transmission in the Anterior Cingulate Cortex Against Peripheral Inflammation-induced Depression - Xiaoyun Qiu; Xiaojie Zhang; Yuanzhi Yang; Minjuan Sun; Xiaoli Da; Jiaying Liu; Rui Wang; Jingjia Liang; Xuhong Jiang; Gang Tian; Qiyuan Shan; Yu Du; et al. (Neuroscience Bulletin, 2026)

New 14,15-dinor- neo -clerodane and neo -clerodane diterpenoids from Ajuga macrosperma Wall. ex benth - Yi-huan Li; Yi-hang Ba; Jian-fen Xiao; Shuai Chen; Tian-qing Zhu; Kai-xiang Liu; Hong-ping He; Hua-yi Jiang; Rui Yang (Natural Product Research, 2026)

Partial sympatry of two interspersed Uroteuthis edulis (Loliginidae) clades reveals cryptic stock structure in the southern Taiwan Strait - Rui-Yi Hong; Lorenzo C. Halasan; Ke-Yang Chang; Chia-Hui Wang; Hsiu-Chin Lin (Fisheries Research, 2026)

Study on spatiotemporal evolution characteristics of temperature field, fracture propagation and oxygen transport in coalfield fire - Fan Tao; Li-Feng Ren; Cai-Ping Wang; Ze-Yang Song; Xin Li; Jin-Rui Wang; Yi-Zhuo Jia; Jun Deng (Fuel, 2026)

Triterpenoids in the leaves of Schisandra chinensis (Turcz.) Baill. treated AD by inducing mitophagy through activation of MCL-1 - Shi-Qi Xu; Xin Meng; Xu Yang; Gang-Tao Bu; Si-Yi Wang; Meng-Meng Li; Yi-Qiang Zhang; Zhi-Chao Hao; Wei Guan; Qi-Shan Chen; Li-Li Zhang; Rui-Yan Wu; et al. (Food Bioscience, 2026)

Erratum to “Evidence of shallow subsurface ice at Tianwen-1 landing site” [Earth and Planetary Science Letters 678 (2026)/EPSL 119832] - Xindong Meng; Ling Zhang; Yi Xu; Iraklis Giannakis; Roberto Bugiolacchi; Jiannan Zhao; Xiaoping Zhang; Qiquan Yang; Rui Chen; Renrui Liu; Xiaoting Xu; Huaqing Cao; et al. (Earth and Planetary Science Letters, 2026)

Nanoflower-like Co3S4/FeOOH heterostructure enables efficient norfloxacin degradation via synergistic radical-non-radical PMS activation - Yuerong Zhou; Ming Yi; Yu Zhao; Rui Yang; He Yan; Xiuwen Cheng (ENGINEERING Environment, 2026)

Contagion and network effects of climate policy on stock markets: evidence from carbon-neutral industry chain sectors - Rui Yang; Cody Yu-Ling Hsiao; Yi-Bin Chiu; Chin Man Chui (Climatic Change, 2026)

Cloning, heterologous expression, and characterization of a metagenome-derived GH10 xylanase with salt and alkali tolerance from Xinjiang saline-alkali soil - Jing Gao; Hua-Lin Li; Mao-Song Li; Zong-Jin Shao; Zheng-Feng Yang; Chan-Jin Li; Zhi-Xin Zhang; Dan Zhu; Zhi-Hua Lv; Rong-Huan Song; Jian-Ling Li; Wei Hu; et al. (Antonie van Leeuwenhoek, 2026)

Transboundary ecological risks and toxicological mechanisms of a fluorinated liquid crystal monomer and aged microplastics - Rui Yang; Sanjeeb Mohapatra; Apple Pui-Yi Chui; Season Si Chen; Mui-Choo Jong (Journal of Hazardous Materials, 2026)

Low-alkali activated Ca2+-KNBC/SA aerogel from waste citrus peel: Efficient and selective removal of Cu(II) and Cd(II) in acidic wastewater - Jiajia Yang; Rui Zhang; Ying Lei; Jian Yang; Maiming Ye; Zhengyu Luo; Hailing Li; Xiaofeng Zhou; Yi Huang; Xinyu Wang; Peng He (Journal of Environmental Management, 2026)

Model-based assessment of impacts of aeration intensity on the water-energy-carbon nexus of a full-scale wastewater treatment plant - Xinhong Han; Lu-Man Jiang; Lifeng Lin; Long Wang; Peng Peng; Jiaming Hu; Jiguang Ying; Yi Yang; Rui Tang; Zhen Zhou (Journal of Environmental Management, 2026)

Insight into the enhancement effect of pristine and amino-functionalized MWCNTs@SiO2 on the CO2 absorption and solar-driven regeneration performance of alkaline deep eutectic solvent based nanofluid system - Wei Wang; Yang Tang; Yi-Ming Chen; Rui-Rui Zhou; Zhang-Mao Hu; Jin-Cheng Huang (Journal of Environmental Chemical Engineering, 2026)

A novel dual-mode sensor based on green-synthesized AuNPs and natural nitrogen-doped CQDs for tobramycin detection: enhanced sensitivity and specificity - Qiang Li; Rui-ling Yin; Xing-yi Yang; Yi-xin Xu; Yan-bing Leng; Xin Liu (Food Research International, 2026)

AI-Facilitated selenium-enriched peptides: Synthesis, bioactivity, virtual screening, and food industry potential, and future prospects - Zhi-Rui Ding; Jun-Wei Chen; Lin-Jie Xiao; Meng-Yu Gao; Jayani Chandrapala; Long Pan; Yang Lin; Hui-Rong Wang; Na Liu; Kang-Yi Zhang; Ai-Mei Liao (Food Bioscience, 2026)

Integrated plastic film and straw mulching enhances potato tuber yield in mountainous regions by optimizing rhizospheric metabolites and root–microbe interactions - Kang Du; Xinyue Yang; Zhenpeng Deng; Xi Lin; Mengyuan Hu; Rui Jiang; Guolian Zheng; Xiaoping Yi; Xun Liu; Changwen Lyu; Jichun Wang (Field Crops Research, 2026)

Enhanced electrocatalytic degradation of concentrated simulated metronidazole wastewater by MIL-101(FeCu)/graphite felt electrodes - Songshan Jiang; Fan Wu; Rui Wen; Lin Xu; Qian Zhong; Meiling Yang; Bai He; Huan Yi; Huan Pang (Chemical Engineering Journal, 2026)

Dynamic electric field modulation via BaTiO3-based staggered-type heterojunction for all-solid-state lithium-sulfur batteries - Yancheng Yang; Sizhe Wang; Fei Liang; Haizhou Zhao; Yi Gu; Rujing Liu; Jian Sun; Yao Yao; Rui Tian; Haojie Song (Chemical Engineering Journal, 2026)

Responses of soil microbial communities in a large vanadium-titanium magnetite tailing dam under half a century of revegetation - Xiaofeng Zhou; Jiajia Yang; Ying Lei; Rui Zhang; Shuming Peng; Sihong Li; Yi Huang; Xinyu Wang; Peicong Zhang; Peng He (Plant and Soil, 2026)

Rapid and Simple Detection of Enterocytozoon Bieneusi Using Lateral Flow Assay Based on Recombinase Polymerase Amplification or Nested PCR Combined with CRISPR–Cas12a - Yi-Yang Liu; Yue-Rong Lv; Jun-Tao Jia; Rong Zhang; Bo Yang; Shi-Yuan Xue; Hasi Bayaer; Alateng Bagen; Rui-Bin Chen; Siqin Tunala; Rui Wang; Yu-Lin Ding; et al. (Acta Parasitologica, 2026)

Reduction of regulatory B cells is associated with high-risk clinical stratification in antiphospholipid syndrome patients - Rui Ma; You-yang Wang; Jing-hong Feng; Wen-yi Li; Yan Long (Immunologic Research, 2026)

Microbiome differentiation and phenotypic variation of Pyropia haitanensis under two contrasting aquaculture environments - Fengjuan Li; Yi Liu; Qijun Luo; Juanjuan Chen; Rui Yang; Wenrong Zhu; Huifeng Cai; Haimin Chen (Aquaculture, 2026)

Multi-stage study of pyrolysis kinetics, combustion characteristics, and fire modeling for selected nature wood species - Yi-Xuan Lin; Qiang Wang; Qi-Xian Li; Qing-Wen Lin; Peng-Rui Man; Shu-Nan Zhou; Yang Li; Jun Deng (Fuel, 2026)

Imidacloprid exposure at population-relevant doses induces hepatic lipid dysregulation: Exploring the role of cGAS-STING pathway-mediated hepatocyte senescence - Yuhan Zhang; Yuqing Dai; Yihong Di; Bing Wu; Xueyan Tian; Limeng Xiong; Zeyang Bai; Jinhao Jia; Jiaming Fu; Xiaoyu Li; Yi Zhao; Hao Hu; et al. (Environmental Research, 2026)

Evidence of shallow subsurface ice at Tianwen-1 landing site - Xindong Meng; Ling Zhang; Yi Xu; Giannakis Iraklis; Roberto Bugiolacchi; Jiannan Zhao; Xiaoping Zhang; Qiquan Yang; Rui Chen; Renrui Liu; Xiaoting Xu; Huaqing Cao; et al. (Earth and Planetary Science Letters, 2026)

Decoupling surface area from function: isolating the dominant role of surface chemistry in superior chlortetracycline adsorption on a low-porous biochar - Qiaohui Peng; Xiangyu Huang; Nannan Wu; Yifan Zhang; Yi Liu; Na Duan; Rui Yang; Dongdong Zhang (Bioresource Technology, 2026)

A New Species of Diaporthe Section Betulicola (Diaporthomycetidae, Diaporthales) From China - Yi Lan Jin; Xing Yu Luo; Kamran Habib; Yu Lin Ren; Qing Yang; Li Li Liu; Chanhom Loinheuang; Yang Chen; Qi Rui Li (New Zealand Journal of Botany, 2026)
A new species in Diaporthaceae, Diaporthe fengtaiensis sp. nov., is described and illustrated from Southwestern China. A comparative morpho‐anatomical study and multilocus phylogenetic analysis (ITS, CAL , HIS , TEF1‐α , TUB2 ) confirmed its position within the section Betulicola of the genus Diaporthe . The taxon is characterized by immersed ascomata (270–420 × 290–410 µm), relatively large asci (70–115 × 9.5–13.5 µm), and 1‐septate, fusiform ascospores (18.5–25.6 × 4.5–6.5 µm). Its positioning in a separate branch in the phylogenetic tree makes it distinct from the other known species of the section. A complete taxonomic treatment, based on two collected specimens, is provided along with molecular phylogenetic analyses.

Noise Characteristics and Shallow Subsurface Structure Detection in Coastal Zones: A Case Study from Dong’ao Island, Zhuhai - Siqing Liu; Sixu Han; Yongzhi Liang; Shuji Yang; Yi Chai; Tongying Hu; Ruifeng Wu; Yu Li; Qingxian Zhao; Zengjia Li; Wei Zhang; Xianqing Wang; et al. (Journal of Marine Science and Engineering, 2026)
Shallow subsurface structure detection in coastal zones serves as a critical foundation for resource development and engineering construction. However, conventional geophysical methods exhibit significant limitations in land–sea transition zones, where pronounced “boundary effects” create substantial “exploration gaps” due to difficulties in merging terrestrial and marine datasets. To achieve truly seamless subsurface imaging across the coastal boundary, this study develops and implements an integrated cross-boundary survey approach utilizing nodal seismometers and seismic ambient noise. At Dong’ao Island, Zhuhai, we deployed a comprehensive seismic profile spanning hillside, sandbeach, and seafloor environments to evaluate the method’s applicability in complex coastal settings systematically. Results demonstrate substantially stronger ambient noise energy in submarine environments compared to terrestrial settings. All stations recorded abundant and stable high-frequency (>1 Hz) noise signals, which are adequate for shallow subsurface imaging. Rayleigh wave dispersion curves extracted via the advanced Frequency-Bessel transform method enabled inversion of a continuous 2D shear-wave velocity profile along the survey line. Bedrock interface depths determined using the Horizontal-to-Vertical Spectral Ratio (HVSR) method showed remarkable consistency with the bedrock morphology revealed by the shear-wave velocity structure, validating the reliability of our approach in coastal environments. This research successfully demonstrates the feasibility of seismic ambient noise imaging as a bridging technique for land–sea exploration, providing an efficient, environmentally friendly, and continuous technical solution to overcome coastal zone exploration challenges.

Synergistic pathogenic mechanisms of EHP and IHHNV co-infection in Litopenaeus vannamei: Insights from RNA-seq analysis - Lin-Rui Chang; Cai-Yi Chen; Fan Yang; Chuan-Yu He; Fan Li; Ting Li; Ling-Jun Si; Dong-Chun Yan (Journal of Invertebrate Pathology, 2026)

Chronic co-exposure to BPA and alcohol synergizes hepatotoxicity via dysregulation of glycerolipid metabolism and ceramide/HtrA2-driven apoptosis in HepG2 cells - Yan Qin Tan; Chia-Lung Shih; Yi-Chia Chen; Sheng-Han Lee; Ji-Rui Yang; Chan-Yen Kuo; Yi-Shiou Chiou (Journal of Hazardous Materials, 2026)

Dual-function Ag2O/Zn-hemin MOF composites for radioactive iodide: performance and mechanism studies for removal and efficient visual detection - Yi-Ting Chen; Xiao-Jun Dai; Wen-Ge Zhang; Wen-Rui Zhang; Shu-Xuan Li; Man-Li He; Kai Chen; Yan Jiao; Peng Wang; Chun-Hui Gong; Yi Yang (Environmental Research, 2026)

Plasma-ball milling assisted core-shell Si@SiOx/SiO2@C hybrid anode enabling highly stable Li-ion storage - Wen-Hua Shi; Zhi-Wen Yin; Zong-Bu Qin; Qing-Qing Yang; Rui-Qing Wang; Zi-Shuo Xia; Zhao-Dong Qiu; Jing Liu; Zhi-Yi Hu; Li-Hua Chen; Yu Li; Bao-Lian Su (Chemical Engineering Journal, 2026)

Gastrin releasing peptide receptor antagonism in the paraventricular nucleus exerts antihypertensive effects in 2K1C rats - Xiao-Min Wang; Jin-Jun Liu; Yi-Pu Wang; Chao Bai; Abdoulaye Issotina Zibrila; Wen-Jie Xia; Rui-Na Yang; Yu-Ming Kang; Xiao-Jing Yu (Toxicology and Applied Pharmacology, 2026)

Assessing pollutant leaching and migration from underground coal gasification residual coke - Yi Cheng; Caifang Wu; Rui Yang; Fangfang Wang; Xiuming Jiang; Shuai Xu (Process Safety and Environmental Protection, 2026)

Rice SINA E3 ligases dichotomously control ERECTA1 ubiquitination and stability to regulate panicle morphogenesis and grain yield - Zi-Qi Lu; Tao Guo; Ying-Jie Cao; Jun-Xiang Shan; Wang-Wei Ye; Nai-Qian Dong; Yi Kan; Yi-Bing Yang; Shuang-Qin Guo; Jie-Jie Lei; Xiao-Rui Mu; Ji-Fu Zhou; et al. (Molecular Plant, 2026)

Performance evaluation of an enhanced air-lift internal circulation anaerobic–aerobic integrated reactor for treating real domestic wastewater - Yi Jiang; Muhammad Younas; Rui Zhang; Yizhi Zhang; Siyi Bian; Mingjie Hu; Die Liang; Linshan Yang; Pan Li; Suhui Xia; Wenyang Tao; Yuji Ma; et al. (Journal of Water Process Engineering, 2026)

Grassland soil seed bank responses to grazing exclusion: a global synthesis - Jishuai Su; Lixin Yu; Rui Tian; Wanbing Liu; Ruolin Zhao; Menghan Niu; Zekai Yang; Yi Zhang; Fengwei Xu; Heyong Liu; Yong Jiang (Journal of Environmental Management, 2026)

Interfacial charge transfer bridge enables high-quality heterojunction for braided coaxial ammonium-ion asymmetric supercapacitors - Jing Xu; Sheng-Jie Wang; Mao-Lan Liao; Zi-Tao Yang; Jia-Peng Hu; Rui-Lai Liu; Jia-Huan Tang; Zhi-Feng Zheng; Yi-Bing Xie (Chemical Engineering Journal, 2026)

Screening of Fecal Bacteroides Strains and Discovery of Bacteroides eggerthii S13-F8 with Protective Effects Against Chemotherapy-Induced Diarrhea - Yi Zhao; Zhengqun Dai; Yanmei Lang; Rui Li; Hongyu Zheng; Jiajia Mi; Xiu He; Jin Liu; Rong Xiang; Xueran Mei; Yang Liu; Yantang Wang; et al. (Probiotics and Antimicrobial Proteins, 2026)

Mechanisms of Action of FUNDC1 in Cerebral Ischemia-Reperfusion Injury - Xin-Yi Zou; Luo-Yang Cai; Jin Zhang; Ying Yuan; Jie Song; Zhao-Duan Hu; Rui Peng; Xiao-Feng Ruan; Xiao-Ming Zhang (Molecular Neurobiology, 2026)

Systematic investigation, expression analysis of TCP transcription factors in eggplant and functional characterization of SmTCP3 gene involved in response to drought stress - Fa-xiang Wan; Yu Zheng; Rong-rong Li; Ying-fan Zhang; Hua-ju Zheng; Ji-qing Li; Yi-min Jiang; Jia-rui Yang; Bo Qi; Jun Gao; Ya-nan Chen; Yu Pan (Genetic Resources and Crop Evolution, 2026)

Cloning, heterologus expression and characterization of a thermophilic and salt tolerant GH11 xylanase from Allostreptomyces psammosilenae YIM DR4008T - Xin-Wei Li; Dan Zhu; Lei Li; Run-Feng Yang; Shi-Yuan Fan; Zhi-Hua Lv; Meng-Di Rao; Rong-Huang Song; Peng Sang; Yi-Rui Yin; Li-Quan Yang (Antonie van Leeuwenhoek, 2026)

Automatic Image Co-registration of Carotid Angiography and Intravascular Optical Coherence Tomography Based on Machine Learning Method: A Pilot Feasibility Study - Hui Xu; Jia-Nan Li; Yan Xu; Jun-Ren Ma; Kang Zong; Rui Zhu; Yi-Hui Cao; Peng-Fei Yang; Rui Zhao; Jian-Min Liu (Annals of Biomedical Engineering, 2026)

Two meroterpenoids from the root bark of Eucalyptus robusta - Yi-Yang Chen; Yong-Xin Wei; Rui-Zhen Chen; Kun-Feng Zhang; Ling-Yi Kong; Ming-Hua Yang (Phytochemistry Letters, 2025)

Effects of sun drying combined with baking processes on the flavor quality of Chongqing Tuocha raw tea - Hongyu Luo; Rui Chang; Shanmin Chen; Yueyun Liu; Yi Wang; Linying Yuan; Juan Yang; Ying Zhang; Ruiqi Duan; Quan Wu; Yingfu Zhong (Food Chemistry, 2025)

Imidacloprid induces abnormal glucose metabolism through NF-κB-mediated apoptosis of pancreatic β cells based on population exposure levels - Zhongyuan Zhang; Jiaming Fu; Yihong Di; Honghui Li; Bing Wu; Xueyan Tian; Meiyan Li; Yuqing Dai; Zhuoheng Shen; Jinhao Jia; Zeyang Bai; Limeng Xiong; et al. (Environmental Research, 2025)

Different Chemical Fertilization Levels Affect Arbuscular Mycorrhizal Fungal Communities in Rhizosphere Soils of Ratoon Sugarcane - Xiao-Juan Qin; Sheng Wang; Ying-Jie Nong; Yi-Hao Kang; Jin-Lian Zhang; Shi-Yuan Zeng; Ting-Su Chen; Yang-Rui Li (Sugar Tech, 2025)

Temporal transcriptomics reveal crucial networks underlying jasmonate-mediated diurnal floret opening and closure in rice - Rui Zhang; Xiaohui Xi; Xiaozhou Hu; Dan Xiang; Yi Wang; Yu Pan; Xi He; Yuhan Zhang; Lilan Hong; Yuanzhu Yang; Ming Zhou (Science China Life Sciences, 2025)

Transcriptomic analysis of the mechanism of male reproductive injuries caused by the mixture of three phthalates in rats - Ling-Zi Xia; Jun-Zhe Yue; Li-Jun Wu; Qian-Ying Jin; Yi-Pei Yang; Jing-Yang Yu; Rui-Zhe Pan; Xin Zhang; Xiao-Ying Wu; Jiayin Zhu; Hai-Tao Gao (Toxicology and Applied Pharmacology, 2025)

NCOA4-dependent ferritinophagy drives perfluorooctanoic acid-triggered renal ferroptosis in chicken embryos - Jie Yang; Xue Wen; Yi-Tong Fu; Chao Li; Hai-Long Chang; Yao-Yao Lu; Xue-Ru Li; Rui-Feng Fan (Journal of Hazardous Materials, 2025)

Integrated assessment of chromium exposure risk from agricultural soils using chemical extraction, in vitro simulation, and mouse bioassay - Peng Xiao; Yi Zhou; Pengfei Wang; Rui Li; Shimao Xiong; Xiyan Jiang; Yunpeng Li; Yue Wu; Yuntao Yang; Xiaolin Cai; Naiyi Yin; Yanshan Cui (Journal of Hazardous Materials, 2025)

Enhanced electrocatalytic oxidation of high-salinity quaternary ammonium compound wastewater using CNTs-(Ru Ir O2)/Ti Anode - Hao-Tian Liu; Han-Qing Zhao; Yi-Rui Yang; Shuang Wu; Jia-Ping Huang; Rui-Han Yu; Hongcheng Bai; Aqiang Ding; Daijun Zhang; Peili Lu (Journal of Environmental Sciences, 2025)

Field-based analysis of CO2 direct expansion heat pump systems for sustainable heating in cold regions: A case study - Yuwei Fan; Yi-Zhou Wang; Pei Li; Xiaolong Li; Jianguo Yang; Xuyan Song; Zhao-Rui Peng; Chunhua Qi; Xin-Rong Zhang (Energy and Buildings, 2025)

Entropy-phase synergy enables stable and high-rate layered oxide cathodes for sodium-ion batteries - Xingyue Yang; Mengfei Du; Jiali Fu; Yi Yang; Zhuo Xiong; Weiyue Li; Liangzhi Li; Jianping Long; Rui Li; Jian Chen; Anjun Hu (Chemical Engineering Journal, 2025)

Ternary eutectic solvents facilitate the production of well-dispersed chitin-glucan nanofibrils from shiitake mushrooms - Rui Zhou; Xingyu Yi; Yi Qin; Ruoyun Wu; Yang Wang; Liang Liu; Yimin Fan (Carbohydrate Polymers, 2025)

Novel laser-driven fast pyrolysis of biomass: Insights into biochar characteristics and applications - Rui Ma; Jintao Luo; Xiaoning Duan; Yuwan Sheng; Shaohui Wang; Deli Zhang; Fang Wang; Shuo Yang; Weiming Yi (Bioresource Technology, 2025)

Marine Hydrogen Pressure Reducing Valves: A Review on Multi-Physics Coupling, Flow Dynamics, and Structural Optimization for Ship-Borne Storage Systems - Heng Xu; Hui-Na Yang; Rui Wang; Yi-Ming Dai; Zi-Lin Su; Ji-Chao Li; Ji-Qiang Li (Journal of Marine Science and Engineering, 2025)
As a zero-carbon energy carrier, hydrogen is playing an increasingly vital role in the decarbonization of maritime transportation. The hydrogen pressure reducing valve (PRV) is a core component of ship-borne hydrogen storage systems, directly influencing the safety, efficiency, and reliability of hydrogen-powered vessels. However, the marine environment—characterized by persistent vibrations, salt spray corrosion, and temperature fluctuations—poses significant challenges to PRV performance, including material degradation, flow instability, and reduced operational lifespan. This review comprehensively summarizes and analyzes recent advances in the study of high-pressure hydrogen PRVs for marine applications, with a focus on transient flow dynamics, turbulence and compressible flow characteristics, multi-stage throttling strategies, and valve core geometric optimization. Through a systematic review of theoretical modeling, numerical simulations, and experimental studies, we identify key bottlenecks such as multi-physics coupling effects under extreme conditions and the lack of marine-adapted validation frameworks. Finally, we conducted a preliminary discussion on future research directions, covering aspects such as the construction of coupled multi-physics field models, the development of marine environment simulation experimental platforms, the research on new materials resistant to vibration and corrosion, and the establishment of a standardized testing system. This review aims to provide fundamental references and technical development ideas for the research and development of high-performance marine hydrogen pressure reducing valves, with the expectation of facilitating the safe and efficient application and promotion of hydrogen-powered shipping technology worldwide.

The multi-omics approach reveals the impact of Temnocephala digitata infection on Macrobrachium rosenbergii - Lianggang Wang; Yan Yang; Libin Huang; Guanghua Huang; Lan Zeng; Xiaohua Lu; Zhide Ruan; Shaokui Yi; Quanxin Gao; Tianhe Lu; Jingkai Qin; Liuchun Lan; et al. (Aquaculture, 2025)

SIRT3 promotes mitophagy to attenuate fumonisin B1-induced chicken hepatocyte senescence and antagonism of lycopene - Yuan-Hang Chang; Ming-Shan Chen; Hong-Mei Zhu; Rui-Qi Liu; Zi-Yan Hu; Shang-Jia Yang; Xue-Qi Wang; Yue Cheng; Yi-Jia Song; Xin-Yue Mao; Jing Zheng; Yi-Bo Wang; et al. (Journal of Hazardous Materials, 2025)

Synergistic engineering of four-pointed star-like layered stacking and oxygen vacancies toward high-efficiency Bi2O2-xSe photocatalysts for the degradation of tetracycline and Congo red - Yao Yang Liu; Zhong Li; Yi Liang; Jing Hao Zhuang; Wen Ji Zhang; Tao Tang; Yin Fen Cheng; Rui Ou; Bao Yue Zhang; Jian Zhen Ou (Journal of Environmental Chemical Engineering, 2025)

Surface oxygen vacancies and their synergy effect with Pt in Pt/CoCeOx promoting H2 activation for furfural hydrogenation - Yu Fang; Rui Wang; Min Tian; Shanyu Yi; Luna Ruan; Xin Duan; Huan Zhang; Zhiqing Yang; Hengqiang Ye; Lihua Zhu (Chemical Engineering Journal, 2025)

Deinococcus lichenicola sp. nov., A Bacterium Isolated from a Lichen Sample - Guo-Hua Chen; Lian-Shuang Xiong; Rui Yang; Shu-Ya Zuo; Qing Yuan; Li-Song Wang; Cheng-Lin Jiang; Xin-Yu Wang; Yi Jiang (Current Microbiology, 2025)

Desulfosporosinus sediminicola sp. nov., an acidophilic sulfate-reducing bacterium isolated from acidic sediments of a disused iron mine site - Sheng-Fang Jiang; Chu-Yi Zhang; Xuan-Wen Lao; Wei-Chao Jia; Tao-Tao Yang; Si-Yu Zhang; Ying-Ying Xie; Pei-Zhe Ye; Rui Lan; Zi-Xiang Lai; Qiang Yang; Li-Nan Huang (Antonie van Leeuwenhoek, 2025)

Effect of primate protection on threatened and endemic vertebrates, plants, ecosystem services, and future climate refugia - Yin Yang; Chen Li; Yi‐Hao Fang; Guo‐Peng Ren; Zhi‐Pang Huang; Yan‐Peng Li; Liang‐Wei Cui; Meng‐Ran Chu‐yuan; Colin A. Chapmman; Cyril C. Grueter; Jian Zhou; Wen‐Bo Yan; et al. (Conservation Biology, 2025)
Primates, 69% of which are threatened with extinction, are the third most specious order of mammals. We used primates as model taxa to examine the umbrella effects of primates on ecosystem services and the protection of other vertebrates and seed plants in Yunnan Province, China. We identified areas of conservation priority for 16 primate species and determined which other threatened and endemic terrestrial vertebrates and seed plants would be protected through a program targeting primate conservation. Areas of high primate species richness were spatially correlated with the distribution of 601 species of threatened and endemic vertebrates and 4010 seed plants. Primate species richness was positively correlated with carbon sequestration and enhanced water and soil conservation and coincided with future areas of climate refugia. If 30% of Yunnan's land area were designated as primate conservation priority areas, then 52.3% of the province's average annual carbon sequestration, 51.7% of its water conservation, 54.1% of its soil retention, and 30‐33% of its climate‐stable areas would be protected. Protecting primates as umbrella taxa uniquely contributes to maintaining biodiversity and ecosystem services that promote ecosystem stability. Although we focused on a single mammalian order in a single region, our approach for umbrella taxa evaluation has broad applicability and can help achieve multiple conservation targets of the Kunming–Montreal Global Biodiversity Framework.

Anti-inflammatory and antinociceptive effects, toxicity, and phytochemical analysis of Beaumontia grandiflora Wall. - Rui Yang; Dan Teng; Ming-rui Yang; Yi-huan Li; Jian-fen Xiao; Qian-ru Zhang; Hong-ping He; Hua-yi Jiang (Natural Product Research, 2025)

Identification and characterization of a new strain of Ictalurid herpesvirus 1 isolated from channel catfish in China - Fei Yu; Jiehua Xu; Sheng Yuan; Yi Yang; Siyang Song; Kai Hao; Rui Yuan; Yu Wang; Xiaohui Chen; Zhe Zhao (Aquaculture, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Subduction-induced crustal growth in the Neoproterozoic continental magmatic arc: Evidence from arc-type high-Mg# diorites and adakitic granitoids in the western Yangtze Block, South China - Rui-Yang Liu; Shao-cong Lai; Yu Zhu; Ren-Zhi Zhu; Min Liu; Jiang-Feng Qin; Fang-yi Zhang; Hang Yang (Precambrian Research, 2025)

Comparative metagenomic analyses of viral genomic diversity and ecosystem functions in extremely acidic copper mine tailings - Pei-Zhe Ye; Qiang Yang; Chu-Yi Zhang; Tao-Tao Yang; Sheng-Fang Jiang; Rui Lan; Shao-Ming Gao; Li-Nan Huang (Journal of Hazardous Materials, 2025)

Ionic liquid modified MOF-808 for efficient adsorption and stable capture of radioactive iodine - Xiao-Jun Dai; Yi-Ting Chen; Wen-Ge Zhang; Shu-Xuan Li; Wen-Rui Zhang; Xiang-Hua Qi; Chun-Hui Gong; Peng Wang; Man-Li He; Yi Yang (Journal of Environmental Management, 2025)

Anion competitive coordination for solvation structure regulation in high-voltage sodium-ion batteries - Bowen Zhu; Jingkai Gao; Simin Li; Wei Zhou; Zhendong Yang; Rui Jin; Yi Zhang; Zixuan Ding; Yanqing Lai; Jie Li; Zhian Zhang (Chemical Engineering Journal, 2025)

Optimizing patterned laser-induced graphene strain sensors via novel piezoresistive modeling and multi-objective analysis - Jia-Chen Shang; Wen-Feng Pan; Wen-Hao Zhao; Heng Yang; Yu-Yi Chen; Rui Wang; Ri-Han Wang; Ling-Yu Sun; Yao-Guang Cao; Shi-Chun Yang (Chemical Engineering Journal, 2025)

Application and identification of monoclonal antibody targeting a novel epitope on p72 protein of African swine fever virus - Yu Dai; Xin Deng; Qi Wang; Ke Yang; Shuqing Yang; Xinran Li; Xinlei Liu; Yuanyuan Yang; Yu Gu; Yi Zheng; Rui Wu (Veterinary Microbiology, 2025)

A new benzoquinone and a new dihydroflavone from Fissistigma polyanthum and their bioactivity - Jian-Fen Xiao; Ming-Rui Yang; Pin-Xiang Fu; Rui Yang; Hong-Ping He; Hua-Yi Jiang (Phytochemistry Letters, 2025)

Screening and discovery of volatile allergenic components from artemisia ordosica in Yulin region of Northern China - Xiaoxue Mo; Cheng Wang; Yi Shan; Siqi Wang; Wen Yang; Zhaomin Xia; Zhanguo Qiao; Tao Zhang; Yuanyuan Ding; Rui Liu; Huaizhen He; Langchong He (Journal of Hazardous Materials, 2025)

TBBPA induced hepatocyte ferroptosis by PCBP1-mediated ferritinophagy - Rui-Qi Liu; Yu-Tong Wu; Yue Cheng; Yuan-Hang Chang; Muhammad Asmat Ullah Saleem; Zi-Yan Hu; Shang-Jia Yang; Xue-Qi Wang; Yi-Jia Song; Xin-Yue Mao; Jing Zheng; Yi-Bo Wang; et al. (Journal of Hazardous Materials, 2025)

A method on the induction of piezoelectricity of PVDF by NaOH: Induced PVDF as ultrafiltration base membrane in interfacial polymerization to enhance the rejection of NaCl - Yuliang Chen; Wenmin Wang; Ying Liang; Chen Chen; Rui Meng; Libo Ba; Yuliang Wu; Yijiang Liu; Weiwei Huang; Fei Yang; Jun Cheng; Xuesong Yi (Desalination, 2025)

Preparation of polyester amide nanofiltration membrane by low concentration hydroxyl monomer induced piperazine through intermolecular interaction - Yuliang Wu; Rui Meng; Chen Chen; Yuliang Chen; Libo Ba; Yijiang Liu; Weiwei Huang; Fei Yang; Jun Cheng; Xuesong Yi; Shitao Zhi; Yajie Pang (Desalination, 2025)

Directed evolution of Escherichia coli Nissle 1917 functioning as a methylotrophic chassis - Li-Hua Liu; Zhiqian Zhang; Bo Xu; Gangzhu Yang; Hua Cui; Lijun Su; Yu Zhang; Baoqing Sun; Yi-Rui Wu; Ao Jiang (Chemical Engineering Journal, 2025)

Combined Toxicity of Heavy Metal Cadmium and Insecticide Chlorpyrifos to Drosophila S2 Cells - Yi-Jun Wu; Kelai Kang; Wenyao Yang; Quangen Wu; Rui Chen; Xingfan Zhou (Bulletin of Environmental Contamination and Toxicology, 2025)

The prognostic significance of histopathological growth patterns in liver metastases undergoing surgery: a systematic review and meta-analysis - Xiang-Yu Wang; Bo Zhang; Yin-Chen Gu; Mei Yang; Bao-Rui Tao; Rong-Quan Sun; Yi-Tong Li; Zhen-Mei Chen; Sen-Feng Ying; Chen-He Yi; Yan Geng; Rui Zhang; et al. (Clinical & Experimental Metastasis, 2025)

The long noncoding RNA VIVIpary promotes seed dormancy release and pre-harvest sprouting through chromatin remodeling in rice - Lu Yang; Yu Cheng; Chao Yuan; Yan-Fei Zhou; Qiao-Juan Huang; Wen-Long Zhao; Rui-Rui He; Jie Jiang; Yi-Chao Qin; Zheng-Tong Chen; Yu-Chan Zhang; Meng-Qi Lei; et al. (Molecular Plant, 2025)

Ectomycorrhizal fungi and biochar promote soil recalcitrant carbon increases under arsenic stress - Xuan Zhang; Yang Liu; Xingran Mo; Zhongliang Huang; Yonghua Zhu; Hui Li; Lijuan Jiang; Zhuming Tan; Zihao Yang; Yi Zhu; Jing Huang; Baiquan Zeng; et al. (Journal of Hazardous Materials, 2025)

Highly sensitive and wash-free human serum albumin detection based on filtration-to-enhancement compound microsphere system - Chen Yang; Xin Zhang; Minjing Mo; Guoqing He; Menglu Gao; Tao Jiang; Yihan Ma; Xiaotong Si; Rui You; Fubing Wang; Yi Yang (Chemical Engineering Journal, 2025)

The recruitment of alkaline phosphatase-positive endogenous neural stem cells enables robust neurogenesis and neural pathways reconstruction following spinal cord injury - Rong-Jie Wu; Jia-Lin Liu; Zheng-Hong Chen; Jing Xu; Ying Ding; Hai-Yang Yu; Chuang-Ran Wu; Shang-Bin Yang; Rui Liu; Yi-Nan Guo; Yue Yang; Ting-Ting Wu; et al. (Chemical Engineering Journal, 2025)

Epigenetics in the modern era of crop improvements - Yan Xue; Xiaofeng Cao; Xiangsong Chen; Xian Deng; Xing Wang Deng; Yong Ding; Aiwu Dong; Cheng-Guo Duan; Xiaofeng Fang; Lei Gong; Zhizhong Gong; Xiaofeng Gu; et al. (Science China Life Sciences, 2025)
Epigenetic mechanisms are integral to plant growth, development, and adaptation to environmental stimuli. Over the past two decades, our comprehension of these complex regulatory processes has expanded remarkably, producing a substantial body of knowledge on both locus-specific mechanisms and genome-wide regulatory patterns. Studies initially grounded in the model plant Arabidopsis have been broadened to encompass a diverse array of crop species, revealing the multifaceted roles of epigenetics in physiological and agronomic traits. With recent technological advancements, epigenetic regulations at the single-cell level and at the large-scale population level are emerging as new focuses. This review offers an in-depth synthesis of the diverse epigenetic regulations, detailing the catalytic machinery and regulatory functions. It delves into the intricate interplay among various epigenetic elements and their collective influence on the modulation of crop traits. Furthermore, it examines recent breakthroughs in technologies for epigenetic modifications and their integration into strategies for crop improvement. The review underscores the transformative potential of epigenetic strategies in bolstering crop performance, advocating for the development of efficient tools to fully exploit the agricultural benefits of epigenetic insights.

Design, synthesis, and antifungal activity of novel pyrazole carboxamide derivatives containing benzimidazole moiety as potential SDH inhibitors - Fei Jin; Feng Peng; Xiang-Yi Kong; Wen-Rui Li; Jian-Qi Chai; Min Chen; Ai-Min Lu; Chun-Long Yang; Guo-Hua Li (Molecular Diversity, 2025)

Sex-Specific Association Between Urinary Metal and Serum Homocysteine Levels in Chinese Older Adults: A Study Based on the Yinchuan Community-Dwelling Elderly Cohort - Zhongyuan Zhang; Kai Wang; Siyu Duan; Yuqing Dai; Meiyan Li; Zhuoheng Shen; Pei He; Rui Wang; ZeYang Bai; JinHao Jia; Limeng Xiong; Xiaoyu Li; et al. (Exposure and Health, 2025)

The role of defatted hydrolyzed egg yolk powder in protecting DHA algal oil - Yingxin Wei; Huan Rui; Xuechun Wang; Cuihua Chang; Yi Wang; Luping Gu; Yujie Su; Yanjun Yang; Junhua Li (Food Chemistry, 2025)

A new insight into the transformation mechanism between reactivity of aqueous monomer and chlorine resistance of polyester-amide nanofiltration membrane - Yuliang Wu; Rui Meng; Chen Chen; Yuliang Chen; Libo Ba; Yijiang Liu; Weiwei Huang; Fei Yang; Yanshan Wang; Jun Cheng; Xuesong Yi; Heng Liang (Desalination, 2025)

Self-oxygenated biomimetic nano-heterojunction combats bacterial biofilm infections via near-infrared triggered ROS storms - Zhengcai Guo; Rui Zhang; Yi Li; Zhiling Chen; Tao Wang; Mingyu Wang; Xiaohong Wang; Yang Cao; Jinchun Tu; Delun Chen; Yang Wang; Qiang Wu (Chemical Engineering Journal, 2025)

CORBES: Radiation belt survey with international small satellite constellation - Ji Wu; Li Deng; Jaan Praks; Marius Anger; Philipp Oleynik; Wojciech Hajdas; Jin-Dong Wang; Shen-Yi Zhang; Bin Zhou; Li Zeng; Jinbin Cao; David Fischer; et al. (Advances in Space Research, 2025)

Phytosterol-enriched Camellia oleifera Abel seed oil obtained by subcritical butane extraction: Physicochemical properties and oxidative stability - Tao Yang; Rui He; Qiuyu Xia; Ilaria Cacciotti; Sameh A. Korma; Weimin Zhang; Guohui Yi (Food Chemistry, 2025)

Study of multifunctional anti-AD ligands: design, synthesis, X-ray crystal structure and biological evaluation of diosmetin derivatives - Aihong Yang; Xiaoyue Yi; Hongwei Zhang; Quanzhen Chen; Rui Shen; Xiaodi Kou (Molecular Diversity, 2025)

Association between sleep quality and serum biomarkers among long-term hot spring bathers: a cross-sectional study - Fen Yang; Yue Zou; Ying-ying Zhang; Hong-xia Li; Yi-hang Xu; Bao-chao Zhang; Lin-xuan Liao; Meng-xi Cao; Rui-xue Wang; Yuan Yuan; Yun Zhou; Da-yong Zeng; et al. (International Journal of Biometeorology, 2025)

Nuclear receptor coactive 4-mediated ferritinophagy: a key role of heavy metals toxicity - Wan-Xue Xu; Xue Wen; Yi-Tong Fu; Jie Yang; Han Cui; Rui-Feng Fan (Archives of Toxicology, 2025)

Monsoon Climate and Anthropogenic Influences Shape Primate Distributions Across the Southeastern Edge of the Qinghai‐Tibet Plateau - Chen Li; Yi‐hao Fang; Guo‐peng Ren; Yan‐peng Li; Zhi‐pang Huang; Liang‐wei Cui; Dionisios Youlatos; Paul A. Garber; Xi‐jun Ni; Hua Zhu; De‐wen Luo; Xin Liu; et al. (Global Change Biology, 2025)
The southeastern edge of the Qinghai‐Tibet Plateau (Yunnan, China) exhibits high biodiversity but stark differences in species richness between its western Longitudinal Range Gorge (LRG) and eastern Yunnan Plateau (YP). We collected distribution data for 16 primate species in Yunnan and analyzed palynological records over the past 20 ka from 21 localities to identify the biogeographic, climatic, and anthropogenic factors that have driven the present‐day distribution of primates in this region. By integrating local ecological knowledge, field surveys, species distribution models, niche utilization rates, and historical vegetation and land use changes, we found that spatial–temporal shifts in the monsoon climate have been a critical factor in shaping primate species richness on the southeastern edge of the Qinghai‐Tibet Plateau. Compared to the YP, the LRG receives more precipitation, has more limited seasonal temperature variation, and has higher minimum temperatures during the coldest month. These conditions have facilitated the development of moist evergreen broadleaf forests, which represent a more suitable habitat for the 14 primate species that inhabit this area. In contrast, the drought‐adapted forests of the YP support only one primate species. Palynological records indicate that the differentiation of the LRG and YP predates human influence. However, over the past 2000 years, anthropogenic habitat loss and hunting have significantly affected the distribution of primates. The ranges of gibbons, langurs, and snub‐nosed monkeys are now restricted to the central and northern regions of the LRG and have disappeared from lower elevations. Lorises have disappeared from their northernmost range. In contrast, the distribution of macaques has remained relatively stable. The Yangtze‐Red River‐24° N line marks the biogeographic boundary of high primate species richness and biodiversity in the LRG and southeastern Yunnan. Our research suggests that changes in monsoon climate have fundamentally shaped contemporary species richness, while recent anthropogenic pressures have caused ‘range contraction’ for many taxa.

A novel framework for river organic carbon retrieval through satellite data and machine learning - Shang Tian; Anmeng Sha; Yingzhong Luo; Yutian Ke; Robert Spencer; Xie Hu; Munan Ning; Yi Zhao; Rui Deng; Yang Gao; Yong Liu; Dongfeng Li (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

BarH1 regulates the expression of conserved odorant-binding protein 22 from Dastarcus helophoroides - Rui-Nan Yang; Dong-Zhen Li; Ao Liu; Yi Wei; Rui-Lin Zhang; Hazem Abdelnabby; Man-Qun Wang (Insect Biochemistry and Molecular Biology, 2025)

Developing a quantitative adulteration discrimination model for forest-grown Panax notoginseng using near-infrared spectroscopy with a dual-branch network - Chao Ji; Haoran Ba; Jinran Dai; Yuxin Xie; Tongyu Zang; Yi Sun; Rui Shi; Liangjuan Zhao; Min Yang; Xiahong He; Xiangyun Ma; Wenjie Zheng (Food Research International, 2025)

Exploration of the regulatory mechanism of pulsed electric field on the aggregation behavior of soybean protein isolates - Rui Wang; Pei-Feng Guo; Jin-Peng Yang; Yan-Yan Huang; Lang-Hong Wang; Jian Li; Song-Yi Lin; Qing-Lin Sheng; Xin-An Zeng; Yong-Xin Teng (Food Hydrocolloids, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Metabolome analysis reveals the involvement of oxylipins in regulating the maturation of conchosporangia in Pyropia haitanensis - Yi Liu; Haike Qian; Shanshan Zhu; Tingting Niu; Qijun Luo; Juanjuan Chen; Rui Yang; Peng Zhang; Tiegan Wang; Haimin Chen (Algal Research, 2025)

Effects of hypoxia on the heart of the juvenile four-finger threadfin (Eleutheronema tetradactylum) based on physiological indicators and transcriptome analysis - Yi Lu; Eric Amenyogbe; Ye- Yang; Zhong-liang Wang; Jing-hui Jin; Rui-tao Xie; Eric Kwabena Droepenu; Jian-sheng Huang (Frontiers in Marine Science, 2025)
This study evaluated the effects of hypoxia on the heart of juvenile four-finger threadfin ( Eleutheronema tetradactylum ) through physiological and transcriptome analysis. Juveniles with an average weight of 122.82 g and length of 24.60 cm were used. Hypoxia significantly increased serum myocardial enzyme activities, including creatine kinase (CK), creatine kinase-MB isoenzyme, lactate dehydrogenase (LDH), and α-hydroxybutyrate dehydrogenase (HDBH). These indicators initially rose and then declined, reflecting cardiac stress and suggesting their potential as early hypoxia biomarkers for real-time aquaculture monitoring. Histological analysis revealed structural damage in myocardial fibers under hypoxia, with increasing severity over time. This underscores the need to minimize oxygen fluctuations to prevent cardiac tissue degeneration. Transcriptome analysis identified upregulated genes involved in cell communication, immune responses, and intracellular signaling, offering potential targets for breeding hypoxia-tolerant species. Kyoto Encyclopedia of Genes and Genomes pathway enrichment analysis highlighted key pathways such as mitogen-activated protein kinase (MAPK), hypoxia-inducible factor-1 (HIF-1), endocytosis, and phagosome formation. The MAPK pathway plays a critical role in cellular stress responses, including survival, proliferation, and apoptosis. Hypoxia-induced activation of MAPKs like ERK, JNK, and p38 regulates stress-responsive genes. HIF-1 signaling regulates oxygen homeostasis, with HIF-1α stabilizing hypoxia-responsive genes such as VEGFA, which promotes vascular remodeling and enhances oxygen delivery. These findings collectively offer practical applications for enhancing aquaculture management, such as monitoring biochemical markers, adopting hypoxia-tolerant breeding, and adjusting environmental conditions to mitigate stress, ensuring better productivity and sustainability. This research provides a foundation for further studies on the molecular mechanisms of hypoxia stress in aquaculture species.

A comprehensive review of deactivation and modification of selective catalytic reaction catalysts installed in cement kilns - Yang Zheng; Yi Xing; Guoliang Li; Jiajia Gao; Rui Li; Qi Liu; Tao Yue (Journal of Environmental Sciences, 2025)

Microplastics and Dechlorane Plus co-exposure amplifies their impacts on soybean plant - Yu Xie; Junzhe Zhang; Yaping Lyu; Yaqi Jiang; Yi Sun; Ziqi Zhang; Haojie Wei; Xingxin Liu; Yukui Rui; Wenlong Yang; Peng Zhang (Environmental Pollution, 2025)

Sleep deprivation stimulates adaptive thermogenesis by activating AMPK pathway in mice - Tian-Shu Zheng; Xin-Ran Gao; Rui-Ping Xu; Yi-Fei Zhao; Zhi-Teng Yang; De-Hua Wang (Journal of Comparative Physiology B, 2025)

Interfacial built-in electric field in 2D Ni(OH)2 heterojunction with the sodium organic compound for enhanced oxygen evolution catalysis - Jiao Zhou; Mingyuan Zhang; Baiyu Ren; Qian Yi; Hao Yu; Baoyue Zhang; Ang Li; Xinyi Hu; Zhong Li; Guanyu Chen; Yinfen Cheng; Rui Gao; et al. (Chemical Engineering Journal, 2025)

Cellulose nanofibers/liquid metal hydrogels with high tensile strength, environmental adaptability and electromagnetic shielding for temperature monitoring and strain sensors - Yushan Zou; Zhengyu Liao; Rui Zhang; Shanshan Song; Yutong Yang; Di Xie; Xinru Liu; Lishi Wei; Yi Liu; Yongming Song (Carbohydrate Polymers, 2025)

Atraric Acid Induces Hair Growth through the Stimulation of Sonic Hedgehog/GLI1 in Human Dermal Papilla Cells - Sultan Pulat; Wonyong Kim; Jee-Hyun Hwang; Rui Zhou; Chathurika D. B. Gamage; Mücahit Varlı; İsa Taş; Yi Yang; So-Yeon Park; Kyung-Min Lim; Jae-Seoun Hur; Hangun Kim (Stem Cell Reviews and Reports, 2025)

Polypeptide-PNP2 in Corn Cervi Pantotrichum Ameliorates Cognitive Impairment in Alzheimer’s Disease Mice by Inhibiting Microglial Cell Activation - Hongyan Pei; Zhongmie He; Rui Du; Yi Yang; Shasha Wu; Wenyan Li; Jian Sheng; Chenyang Han (Molecular Neurobiology, 2025)

A singular spectrum analysis-enhanced BiTCN-selfattention model for runoff prediction - Wen-chuan Wang; Feng-rui Ye; Yi-yang Wang; Miao Gu (Earth Science Informatics, 2025)

Leifsonia stereocauli sp. nov., Isolated from Stereocaulon tomentosum Fr. Lichen - Shu-Ya Zuo; Lian-Shuang Xiong; Qing Yuan; Guo-Hua Chen; Rui Yang; Li-Song Wang; Cheng-Lin Jiang; Xin-Yu Wang; Yi Jiang (Current Microbiology, 2025)

AHR activation relieves deoxynivalenol-induced disruption of porcine intestinal epithelial barrier functions - Zi-Yan Hu; Shang-Jia Yang; Yuan-Hang Chang; Xue-Qi Wang; Rui-Qi Liu; Fu-Wei Jiang; Ming-Shan Chen; Jia-Xin Wang; Shuo Liu; Hong-Mei Zhu; Yu-Sheng Shi; Yi Zhao; et al. (Journal of Hazardous Materials, 2024)

Molecular engineering in thizolo[5,4-d]thiazole-based donor-acceptor covalent organic framework Induced high-efficient photosynthesis of H2O2 - Ding-Ming Xue; Yi-Jun Zhang; Jing-Wen Chen; Hao Yang; Rui-Jie Xie; Shi-Chao Qi; Yuan-Qing Bu; Fei Liu; Hou-Hu Zhang; Jacques Lalevée (Chemical Engineering Journal, 2024)

Community of Arbuscular Mycorrhizal Fungi in the Rhizosphere Soils with Different Generations of Hybridized Progeny of Wild Erianthus arundinaceus and Sugarcane - Jin-Lian Zhang; Yi-Hao Kang; Juan Song; Huan-Ying Xu; Wei Zhang; Ying-Jie Nong; Qian Wang; Qin-Nan Wang; Ting-Su Chen; Yang-Rui Li (Sugar Tech, 2024)

Muscone inhibits angiotensin II–induced cardiac hypertrophy through the STAT3, MAPK and TGF-β/SMAD signaling pathways - Yi-jiang Liu; Jia-jia Xu; Cui Yang; Yan-lin Li; Min-wei Chen; Shi-xiao Liu; Xiang-hui Zheng; Ping Luo; Rui Li; Di Xiao; Zhong-gui Shan (Molecular Biology Reports, 2024)
Background Muscone is a chemical monomer derived from musk. Although many studies have confirmed the cardioprotective effects of muscone, the effects of muscone on cardiac hypertrophy and its potential mechanisms are unclear.The aim of the present study was to investigate the effect of muscone on angiotensin (Ang) II-induced cardiac hypertrophy. Methods and results In the present study, we found for the first time that muscone exerted inhibitory effects on Ang II-induced cardiac hypertrophy and cardiac injury in mice. Cardiac function was analyzed by echocardiography measurement, and the degree of cardiac fibrosis was determined by the quantitative real-time polymerase chain reaction (qRT-PCR), Masson trichrome staining and western blot assay. Secondly, qRT-PCR experiment showed that muscone attenuated cardiac injury by reducing the secretion of pro-inflammatory cytokines and promoting the secretion of anti-inflammatory cytokines. Moreover, western blot analysis found that muscone exerted cardio-protective effects by inhibiting phosphorylation of key proteins in the STAT3, MAPK and TGF-β/SMAD pathways. In addition, CCK-8 and determination of serum biochemical indexes showed that no significant toxicity or side effects of muscone on normal cells and organs. Conclusions Muscone could attenuate Ang II-induced cardiac hypertrophy, in part, by inhibiting the STAT3, MAPK, and TGF-β/SMAD signaling pathways.

Chang’E-7 Lunar Soil Water Molecule Analyzer (LSWMA) Prototype for High-Precision Measurement of Water Content and Hydrogen Isotope Ratio - Rui Chen; Wenzhen Lu; Xiang Li; Xingping Wang; Kan Chen; Chi Zhang; Nailiang Cao; Zhenyu Xu; Yi Xu; Ruifeng Kan; Renrui Liu; Qiquan Yang; et al. (Journal of Earth Science, 2024)

The fate of organic compounds in organic waste during torrefaction and implications for its valorization - Yi Hu; Rui Yang; Yiping Wu; Xuejiao Chen; Wei Lin; Hong Wang; Zhiyong Qi; Dongdong Zhang; Lin Ouyang (Environmental Pollution, 2024)

EtROP38 suppresses apoptosis of host cells infected with Eimeria tenella by inhibition of the p38MAPK pathway - Bu-ting Duan; Hao-yu Zhang; Zi-hao Song; Xiao-yi Han; Kai-ling Cui; Tong Xu; Yu Zhang; Yong-juan Zhao; Xuan Lei; Fan Tan; Lu-lu Guo; Hui-lin Yang; et al. (Veterinary Parasitology, 2024)

A global urban heat island intensity dataset: Generation, comparison, and analysis - Qiquan Yang; Yi Xu; TC Chakraborty; Meng Du; Ting Hu; Ling Zhang; Yue Liu; Rui Yao; Jie Yang; Shurui Chen; Changjiang Xiao; Renrui Liu; et al. (Remote Sensing of Environment, 2024)

Corrigendum to “Euphpepluone S, a new lathyrane diterpenoid with anti-inflammatory activity from Euphorbia peplus L.” [Phytochem. Lett. 55 2023, 61–66] - Shi-Peng Guan; Ying Yang; Mao Sun; Min Cai; Xue-Xue Pu; Jian-Yi Huang; Ping Yi; Lin Liu; Ming-Rui Yuan; Yuan-Yuan Cheng; Ying-Tong Di (Phytochemistry Letters, 2024)

Freshwater microconchids from the Tanzhuang Formation (Middle-Late Triassic) in North China - Hao Yang; Yue Su; Hui-Jun Chen; Yi-Ran Cao; Meng-Yang Zhang; Rui Li; Dao-Liang Chu (Palaeoworld, 2024)

Genesis of high-Al chromitites from Xiaosuihe peridotite (Central Jilin Province, NE China): Implication for initial subduction of the Paleo-Asian ocean - Bing-Qian Ding; Fu-Ping Pei; Jing-Yang Wei; Jin-Rui Zhang; Zi-Cheng Guan; Kai Song; Tian-Jiao Sang; Peng-Yi Li (Lithos, 2024)

An effective potential Bifidobacterium animalis F1-7 delivery strategy: Supramolecular hydrogel - sodium alginate/tryptophan-Sulfobutylether-β-cyclodextrin (Alg/Trp-SBE-β-CD) - Xiaoyang Huang; Jing Wang; Rui Liu; Chunrong Yang; Yanchun Shao; Xiaohong Wang; Huaxi Yi; Youyou Lu (Food Hydrocolloids, 2024)

Use of modified poly-epoxysuccinic acid as an efficient scale inhibitor to control CaSO4 scaling in NF processes: Performance and mechanisms - Xinyuan Yi; Shumin Yang; Xin He; Zhiwei Wang; Min Rui; Yulin Tang (Desalination, 2024)

Polystyrene shell-based “coconut-like” and “pomegranate-like” microencapsulated phase change materials: Formation mechanism, thermal conductivity/stability enhancement and their application in thermal management - Wei Zhang; Rui Pan; Jihua Yang; Mengru Liu; Yunle Yao; Awang Zhang; Yi Gong; Zhengya Gan; Rui Hu; Jianjun Ding; Lin Chen; Xian Zhang; et al. (Chemical Engineering Journal, 2024)

Cyclodextrin-based host-guest hierarchical fire retardants: Synthesis and novel strategy to endow polylactic acid fire retardancy and UV resistance - Jing Zhang; Xiuqin Zhang; Rui Wang; Wenqing Wang; Hui Zhao; Shuo Yang; Zhenfeng Dong; De-Yi Wang; Ye-Tang Pan (Carbohydrate Polymers, 2024)

Associations between multiple urinary metals and metabolic syndrome: Exploring the mediating role of liver function in Chinese community-dwelling elderly - Yuqing Dai; Siyu Duan; Rui Wang; Pei He; Zhongyuan Zhang; Meiyan Li; Zhuoheng Shen; Yue Chen; Yi Zhao; Huifang Yang; Xiaoyu Li; Rui Zhang; et al. (Journal of Trace Elements in Medicine and Biology, 2024)

The transcriptional changes of LrgA discriminates the responsiveness of Staphylococcus aureus towards blue light from that of photodynamic inactivation - Ruili Yang; Yi Xu; Jinchun Xu; Yali Li; Xiaoxiao Wan; Rui Kong; Chao Ding; Han Tao; Hui-Li Wang (Journal of Photochemistry and Photobiology B: Biology, 2024)

Effects of ammonia nitrogen stress on the physiological, biochemical, and metabolic levels of the gill tissue of juvenile four-finger threadfin (Eleutheronema tetradactylum) - Jing-hui Jin; Eric Amenyogbe; Ye Yang; Zhong-liang Wang; Yi Lu; Rui-tao Xie; Eric Kwabena Droepenu; Jian-sheng Huang (Aquatic Toxicology, 2024)

An information quantity and machine learning integrated model for landslide susceptibility mapping in Jiuzhaigou, China - Yunjie Yang; Rui Zhang; Tianyu Wang; Anmengyun Liu; Yi He; Jichao Lv; Xu He; Wenfei Mao; Wei Xiang; Bo Zhang (Natural Hazards, 2024)

Phosphorylation of RasGRP1 by Shc3 prevents RasGRP1 degradation and contributes to Ras/c-Jun activation in hepatocellular carcinoma - Xinran Zhang; Yun Liu; Rui Yang; Yuanyuan Guo; Meiling Yan; Ying Xiao; Yunzhuo Dong; Ruixia Zhang; Yinpeng Qin; Yishan Bu; Yi Zhang; Huier Gao (Molecular and Cellular Biochemistry, 2024)

Comparison of the Intestinal Microbiota Composition and Function of Red Claw Crayfish (Cherax quadricarinatus) Cultured in Ponds and Rice Fields - Libin Huang; Tianhe Lu; Xiaohua Lu; Jingu Shi; Yin Huang; Xuesong Du; Dapeng Wang; Yi Liang; Yanju Lei; Lianggang Wang; Rui Wang; Huizan Yang (Fishes, 2024)
The growth environment significantly influences the intestinal microbiota of aquatic organisms. We investigated the composition and functional differences in the intestinal microbiota of red claw crayfish (Cherax quadricarinatus) in rice fields (RB) and ponds (PB) by 16S rDNA high-throughput sequencing technology. The results indicate that the Shannon, Simpson, Sobs, Chao1, and ACE indices of PB are all higher than those of RB, demonstrating greater diversity and richness of intestinal microbiota. The dominant phyla in the intestinal microbiota of the Cherax quadricarinatus were Proteobacteria, Tenericutes, and Firmicutes. Tenericutes and Proteobacteria were significantly more abundant in the RB than in the PB, while Planctomycetes and Firmicutes were significantly more abundant in the PB than in the RB. The results of network correlation analysis indicate that Proteobacteria and Firmicutes exhibit strong connectivity with other microbial groups in the gut microbiota of Cherax quadricarinatus, showing significant centrality. They play an important role in the interactions within the gut microbiota community. The dominant bacterial genera in the Cherax quadricarinatus’s gut were Citrobacter, Candidatus_Bacilloplasma, and Clostridium_sensu_stricto_1. The abundance of the genus Clostridium was significantly higher in the PB than in the RB, whereas the abundance of Candidatus_Hepatoplasma and Vibrio was significantly lower in the PB than in the RB. The prediction function of KEGG enrichment showed that the abundance of Amino acid metabolism, Biosynthesis of Other Secondary Metabolites, Transport and Catabolism, Cancers, and Nervous System, Substance Dependence were significantly higher in the PB, while the infectious diseases pathway was enriched in the RB. In summary, our results revealed significant differences in the composition and diversity of intestinal microbiota in the Cherax quadricarinatus between rice paddy and pond farming environments. The intestinal microbiota of the Cherax quadricarinatus grown in pond environments exhibit higher diversity and stability, manifested by an increase in beneficial bacteria abundance and a decrease in opportunistic pathogens. These findings significantly improve understanding of the complex relationship among Cherax quadricarinatus, intestinal microbiota, and the environment.

Synergy of pollution reduction and carbon abatement of the 8 urban agglomerations in China: Status, dynamic evolution, and Spatial-temporal characteristics - Tiantian Yang; Lan Yi; Shuai Yan; Rui Zhang; Xiyu Wang (Resources Policy, 2024)

Positive temperature coefficient material based on silicone rubber/ paraffin/ graphite/ carbon nanotubes for wearable thermal management devices - Jian-Min Hao; Yin-Fa Yang; Yi-Tao Shen; Rui Zhou; Wei Zhang; Hua Chen; Wen-Long Cheng (Chemical Engineering Journal, 2024)

Methylene Blue Pretreatment Protects Against Repeated Neonatal Isoflurane Exposure-Induced Brain Injury and Memory Loss - Chongyun Wu; Qianting Deng; Ling Zhu; Timon Cheng-yi Liu; Rui Duan; Luodan Yang (Molecular Neurobiology, 2024)

Ent-eudesmane sesquiterpenoids with anti-neuroinflammatory activity from the marine-derived fungus Eutypella sp. F0219 - Zhong-Ping Jiang; Rui Su; Meng-Ting Chen; Jun-Yi Li; Han-Yu Chen; Lu Yang; Fei-Fei Liu; Jin Liu; Cong-Jun Xu; Wan-Shan Li; Yong Rao; Ling Huang (Phytochemistry, 2024)

Bi-directional association between outdoor or social activities and cognitive function: do the PM2.5 exposure catalyze the detrimental inactivity-poor cognition cycle? - Yuling Jiang; Yifei Wu; Yang Hu; Shaojie Li; Longbin Ren; Jingjing Wang; Mingzhi Yu; Rui Yang; Zhouwei Liu; Nan Zhang; Kejia Hu; Yunquan Zhang; et al. (Environmental Research, 2024)

A new Late Devonian plant assemblage in West Junggar, Xinjiang, China and its floral evolution during the Devonian - Bing-Cai Liu; Kai Wang; Rui-Wen Zong; Jiao Bai; Yao Wang; Ning Yang; Yi Wang; Hong-He Xu (Review of Palaeobotany and Palynology, 2024)

Two new steroids with cytotoxicities from fungus Acrocalymma cycadis - Li-Bin Lin; Deng-Gao Zhu; Ting Yang; Rui Han; Jia-Yao Hu; Wei Shi; Ze-Yi Li; Xiao-Ling Wang; Jian Xiao (Phytochemistry Letters, 2024)

Enteral nutrition in the management of acute pancreatitis: Modulates gut microbiome and alleviates inflammation - Fang-Yuan Yang; Yi-Jing Cai; Xiao-Ying Niu; Shun-Fu Wang; Yu-Qi Wang; Sabola Eluby Esmie; Rui-Cong Chen; Sheng-Jie Dai; Hong-Ru Kong; Hong-Wei Sun; Ke-Qing Shi (Food Bioscience, 2024)

IL-6/STAT3 axis is hijacked by GCRV to facilitate viral replication via suppressing type Ⅰ IFN signaling - Liang Hu; Yang Xu; Qiu-Shi Zhang; Xiao-Ying Chen; Chun Li; Rui Chen; Guo-Li Hou; Zhao Lv; Tiao-Yi Xiao; Jun Zou; Hong-Quan Wang; Jun-Hua Li (Fish & Shellfish Immunology, 2024)

Geochemistry of metabasite in Mariana forearc serpentinite mudflows documents interactions between serpentinizing fluid and subducted seamount basalts - Rui-Peng Zhao; Hong-Yan Li; Jeffrey G. Ryan; Xun Wei; Sheng-Xiong Yang; Yi-Gang Xu (Chemical Geology, 2024)

Regulatory effect of Yinchenhao decoction on bile acid metabolism to improve the inflammatory microenvironment of hepatocellular carcinoma in mice - Jian Shi; Lin Zhu; Bang-Yi Tang; Wan-Qing Yang; Sheng-Yan Xi; Chen-Long Zhang; Peng-Fei Li; Yu-Jie Wang; Kai-Hang Guo; Jing-Ru Huang; Chen-Rui Huang; Zhou-Xin Yu; et al. (Journal of Natural Medicines, 2024)

Biotemplated fabrication of N/O co-doped porous carbon confined spinel NiFe2O4 heterostructured mimetics for triple-mode sensing of antioxidants and ameliorating packaging properties - Yuan Gao; Juan Wang; Lin-Lan Zhao; Bo-Yi Yuan; Ya-Nan Kong; Jing-Jing Luo; Shu-Chang Zhao; Wei-Ming Yang; Rui-Lin Liu (Food Chemistry, 2024)

Fly ash-dominated High-Strength Engineered/Strain-Hardening Geopolymer Composites (HS-EGC/SHGC): Influence of alkalinity and environmental assessment - Jian-Cong Lao; Rui-Yang Ma; Ling-Yu Xu; Yang Li; Yi-Nong Shen; Jie Yao; Yan-Shuai Wang; Tian-Yu Xie; Bo-Tao Huang (Journal of Cleaner Production, 2024)

Finite element modeling and analysis of effect of preexisting cervical degenerative disease on the spinal cord during flexion and extension - Meng-lei Xu; Yi-ting Yang; Hui-zi Zeng; Yu-ting Cao; Liang-dong Zheng; Chen Jin; Shi-jie Zhu; Rui Zhu (Medical & Biological Engineering & Computing, 2024)

Serum Uric Acid Levels and Outcome of Acute Ischemic Stroke: a Dose–Response Meta-analysis - Peng Zhang; Rui Wang; Yang Qu; Zhen-Ni Guo; Qing Zhen; Yi Yang (Molecular Neurobiology, 2024)

The immune response of Caspase-3 gene in infectious hypodermal and hematopoietic necrosis virus (IHHNV) infection of Litopenaeus vannamei - Cai-Yi Chen; Ning Yang; Chuanyu He; Yang Gao; Lin-Rui Chang; Ting Li; Ling-Jun Si; Dong-Chun Yan (Aquaculture, 2024)

Long-term MNNG exposure promotes gastric carcinogenesis by activating METTL3/m6A/miR1184 axis-mediated epithelial-mesenchymal transition - Tong Liu; Yan-lu Feng; Rui-ying Wang; Sheng Yang; Yi-ling Ge; Tian-yi Zhang; Jie Li; Cheng-yun Li; Ye Ruan; Bin Luo; Ge-yu Liang (Science of The Total Environment, 2024)

PD-L1 expression guidance on sintilimab versus pembrolizumab with or without platinum-doublet chemotherapy in untreated patients with advanced non-small cell lung cancer (CTONG1901): A phase 2, randomized, controlled trial - Si-Yang Maggie Liu; Jie Huang; Jia-Yi Deng; Chong-Rui Xu; Hong-Hong Yan; Ming-Yi Yang; Yang-Si Li; E-E Ke; Ming-Ying Zheng; Zhen Wang; Jia-Xin Lin; Bin Gan; et al. (Science Bulletin, 2024)

Two new monoterpenoids from the roots of Paeonia lactiflora and their neuroprotective activities - Bo Fu; Jin-Ling Zhang; Xin Meng; Jia-Tong Wu; Yan Liu; Yu-Qing Wang; Yi-Qiang Zhang; Juan Pan; Wei Guan; Rui-Feng Fan; Anam Naseem; Hai-Xue Kuang; et al. (Phytochemistry Letters, 2024)

Heat stress enhances the occurrence of erythromycin resistance of Enterococcus isolates in mice feces - Lingxian Yi; Rui Xu; Xiaowu Yuan; Zining Ren; Huihui Song; Huamin Lai; Zhihua Sun; Hui Deng; Bo Yang; Daojin Yu (Journal of Thermal Biology, 2024)

Hierarchical porous UiO-66 composites modified by dual competitive strategy for adsorption of oxytetracycline - Tao He; Yi Wang; Rui Han; Xiaodong Li; Shihai Cui; Jing Yang (Journal of Environmental Chemical Engineering, 2024)

Anti-inflammasome bio-heterojunction (AI-bioHJ): Revolutionizing diabetic wound healing with in situ self-transformation and programmed gas therapy - Fan Yang; Rui Shu; Bin Li; Wenyu Dai; Wanxi Chen; Jiamin Sun; Ding Bai; Weizhong Yang; Yi Deng (Chemical Engineering Journal, 2024)

The Community of Arbuscular Mycorrhizal Fungi in Sugarcane Rhizosphere Soils in Guangxi, China - Jin-Lian Zhang; Juan Song; Yi-Hao Kang; Yun-Ying Wen; Ying-Jie Nong; Qian Wang; Xiao-Juan Qin; Ting-Su Chen; Yang-Rui Li (Sugar Tech, 2024)

Novel phenolic metabolites isolated from plant endophytic fungus Fusarium guttiforme - Jing-Yi Yue; Rui Wang; Tao Xu; Ju-Tao Wang; Yang Yu; Bai-Xiang Cai (Natural Product Research, 2024)

Diversified cropping systems with complementary root growth strategies improve crop adaptation to and remediation of hostile soils - Wei-Ping Zhang; Surigaoge Surigaoge; Hao Yang; Rui-Peng Yu; Jin-Pu Wu; Yi Xing; Yinglong Chen; Long Li (Plant and Soil, 2024)

Fungus reduces tetracycline-resistant genes in manure treatment by predation of bacteria - Lei Liu; Qianxi Yin; Yu Hou; Rui Ma; Yi Li; Zhenyu Wang; Ganggang Yang; Yu Liu; Hailei Wang (Science of The Total Environment, 2024)

Square-wave alternating voltage driving promotes nanowire-assisted electroporation inactivation and fouling resistance of pathogenic bacteria for water disinfection - Ying-Wen Lu; Yang Wang; Yi-Rui Liu; Hai Liu (Chemical Engineering Journal, 2024)

Integrative transcriptomic and metabolomic analyses reveal the phenylpropanoid and flavonoid biosynthesis of Prunus mume - Rui Wu; Chengcheng Qian; Yatian Yang; Yi Liu; Liang Xu; Wei Zhang; Jinmei Ou (Journal of Plant Research, 2024)

Human activity and climate change accelerate the extinction risk to non‐human primates in China - Wen‐Bo Li; Yang Teng; Ming‐Yi Zhang; Ying Shen; Jia‐Wen Liu; Ji‐Wei Qi; Xiao‐Chen Wang; Rui‐Feng Wu; Jin‐Hua Li; Paul A. Garber; Ming Li (Global Change Biology, 2024)
Human activity and climate change affect biodiversity and cause species range shifts, contractions, and expansions. Globally, human activities and climate change have emerged as persistent threats to biodiversity, leading to approximately 68% of the ~522 primate species being threatened with extinction. Here, we used habitat suitability models and integrated data on human population density, gross domestic product (GDP), road construction, the normalized difference vegetation index (NDVI), the location of protected areas (PAs), and climate change to predict potential changes in the distributional range and richness of 26 China's primate species. Our results indicate that both PAs and NDVI have a positive impact on primate distributions. With increasing anthropogenic pressure, species' ranges were restricted to areas of high vegetation cover and in PAs surrounded by buffer zones of 2.7–4.5 km and a core area of PAs at least 0.1–0.5 km from the closest edge of the PA. Areas with a GDP below the Chinese national average of 100,000 yuan were found to be ecologically vulnerable, and this had a negative impact on primate distributions. Changes in temperature and precipitation were also significant contributors to a reduction in the range of primate species. Under the expected influence of climate change over the next 30–50 years, we found that highly suitable habitat for primates will continue to decrease and species will be restricted to smaller and more peripheral parts of their current range. Areas of high primate diversity are expected to lose from 3 to 7 species. We recommend that immediate action be taken, including expanding China's National Park Program, the Ecological Conservation Redline Program, and the Natural Forest Protection Program, along with a stronger national policy promoting alternative/sustainable livelihoods for people in the local communities adjacent to primate ranges, to offset the detrimental effects of anthropogenic activities and climate change on primate survivorship.

CD4 is an important host factor for Japanese encephalitis virus entry and replication in PK-15 cells - Qi Wang; Shuqing Yang; Ke Yang; Xinran Li; Yu Dai; Yi Zheng; Sanjie Cao; Qigui Yan; Xiaobo Huang; Yiping Wen; Qin Zhao; Senyan Du; et al. (Veterinary Microbiology, 2023)

Effects of Mixed Cropping on Sugarcane Growth and the Community of Arbuscular Mycorrhizal Fungi - Ying-Jie Nong; Qian Wang; Juan Song; Jin-Lian Zhang; Xiao-Juan Qin; Yi-Hao Kang; Xiang-Hua Wei; Ting-Su Chen; Yang-Rui Li (Sugar Tech, 2023)

The Role of Cystathionine-β-Synthase, H2S, and miRNA-377 in Hypoxic-Ischemic Encephalopathy: Insights from Human and Animal Studies - Chun-Yang Liu; Hisham Al-Ward; Ning Liu; Francine Ngaffo Mekontso; Wei Chen; Wenxia Gao; Chunxue Zhang; Abduh Murshed; Zi-Rui Yu; Orion Fan; Yi Eve Sun; Hui Xu (Journal of Molecular Neuroscience, 2023)

Classification of Glomerular Pathology Images in Children Using Convolutional Neural Networks with Improved SE-ResNet Module - Xiang-Yong Kong; Xin-Shen Zhao; Xiao-Han Sun; Ping Wang; Ying Wu; Rui-Yang Peng; Qi-Yuan Zhang; Yu-Ze Wang; Rong Li; Yi-Heng Yang; Ying-Rui Lv (Interdisciplinary Sciences: Computational Life Sciences, 2023)

Prevalence of Ureaplasma species among patients at a tertiary hospital in China: a 10-year retrospective study from 2013 to 2022 - Ziran Wang; Mingqi Xia; Yu Chen; Zhuo Yang; Jie Yi; Lingjun Kong; Han Zhang; Guoju Luo; Rui Li; Yaling Dou (European Journal of Clinical Microbiology & Infectious Diseases, 2023)

Development characteristics and failure modes of reactivated ancient landslides in the Sichuan–Tibet transportation corridor, China - Rui-an Wu; Yong-shuang Zhang; Chang-bao Guo; San-shao Ren; Xin Yao; Xiao-yi Liu; Zhi-hua Yang; Guo-liang Du (Journal of Mountain Science, 2023)

Quantitative Estimation on Methane Storage Capacity of Organic-Rich Shales from the Lower Silurian Longmaxi Formation in the Eastern Sichuan Basin, China - Xiaowen Guo; Tao Luo; Tian Dong; Rui Yang; Yuanjia Han; Jizheng Yi; Sheng He; Zhiguo Shu; Hanyong Bao (Journal of Earth Science, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

The hepatoprotective effects of plant-based foods based on the “gut–liver axis”: a prospective review - Qiongdan Hu; Wan Liao; Zhen Zhang; Sanjun Shi; Shuguang Hou; Ningping Ji; Xinjie Zhang; Qian Zhang; Yangyang Liao; Linghui Li; Zongping Zhu; Yi Chen; et al. (Critical Reviews in Food Science and Nutrition, 2023)

Development of a duplex PCR for the simultaneous detection of EHP and IHHNV and analysis of the correlation between these two pathogens - Yang Gao; Cai-Yi Chen; Zheng Cao; Ru-Qing Yuan; Lin-Rui Chang; Ting Li; Ling-Jun Si; Dong-Chun Yan; Fan Li (Journal of Invertebrate Pathology, 2023)

Influence of urban extent discrepancy on the estimation of surface urban heat island intensity: A global-scale assessment in 892 cities - Qiquan Yang; Yi Xu; Xiaohua Tong; Ting Hu; Yue Liu; T.C. Chakraborty; Rui Yao; Changjiang Xiao; Shurui Chen; Zonghan Ma (Journal of Cleaner Production, 2023)

Strategy of functional nucleic acids-mediated isothermal amplification for detection of foodborne microbial contaminants: A review - Jie Zhou; Teng-Yu Wang; Zhi Lan; Han-Jie Yang; Xing-Jian Ye; Rui Min; Zhao-Hui Wang; Qing Huang; Jing Cao; Yu-E Gao; Wen-Long Wang; Xiu-Lan Sun; et al. (Food Research International, 2023)

Macroscale insights into heterogeneous hydrate formation and decomposition behaviors in porous media - Xuan Kou; Xiao-Sen Li; Yi Wang; Rui Xu; Zhao-Yang Chen (Chemical Engineering Journal, 2023)

A petal–cylindrical seismic metamaterial occupying low-frequency wide bandgaps in horizontally stratified soils - Muhammad Muzamil; Hongwu Yang; Rui Xu; Yi Zeng; Pai Peng; Qiujiao Du (Wave Motion, 2023)

Diversity and function of mountain and polar supraglacial DNA viruses - Yongqin Liu; Nianzhi Jiao; Kevin Xu Zhong; Lin Zang; Rui Zhang; Xiang Xiao; Yi Shi; Zhihao Zhang; Ye Tao; Liping Bai; Bianli Gao; Yunlan Yang; et al. (Science Bulletin, 2023)

Neolignan derivatives from Penthorum chinense with antitumor activity in human colorectal cancer cells by regulating Wnt/β-catenin signaling pathway - Mengqi Lu; Jingya Ruan; Rui Yu; Ying Zhang; Wei Zhao; Dingshan Yang; Wanxia Wang; Yi Zhang; Tao Wang (Phytochemistry, 2023)

A new norditerpenoid and other components from Ajuga macrosperma and their bioactivity - Yi-Huan Li; Qian-Ru Zhang; Dan Teng; Hong-Ping He; Rui Yang; Hua-Yi Jiang (Phytochemistry Letters, 2023)

Association between urinary neonicotinoid insecticide levels and dyslipidemia risk: A cross-sectional study in Chinese community-dwelling elderly - Jian Sun; Pei He; Rui Wang; Zhong-Yuan Zhang; Yu-Qing Dai; Xiao-Yu Li; Si-Yu Duan; Cai-Ping Liu; Hao Hu; Guang-Jun Wang; Yan-Ping Zhang; Fei Xu; et al. (Journal of Hazardous Materials, 2023)

Recent advances of triplet–triplet annihilation upconversion in photochemical transformations - Jihao Jin; Tianjun Yu; Jinping Chen; Rui Hu; Guoqiang Yang; Yi Zeng; Yi Li (Current Opinion in Green and Sustainable Chemistry, 2023)

Synchronous regulation of Schottky/p-n dual junction in Prussian blue-derived Janus heterostructures: A path to ultrafast long life potassium ion batteries - Shou-Shan Mai; Kai-Yuan Hsiao; Yi-Chun Yang; Ying-Rui Lu; Ming-Yen Lu; Yi-Yen Hsieh; Che-Bin Chang; Hsing-Yu Tuan (Chemical Engineering Journal, 2023)

Photobiomodulation: A Potential Non-invasive Method to Alleviate Neurological Events Following COVID-19 Infection - Chongyun Wu; Timon Cheng-Yi Liu; Rui Duan; Luodan Yang (Neuroscience Bulletin, 2023)

Flat-leaf submerged plants are more sensitive to invasion intensity and water nutrition levels than needle-leaf ones - Yi-Luan Shen; Shu-Yu Zhang; Xiao-Fei Yuan; Kai Sun; Jing-Fang Cai; Jing-Jing Xue; Yu Zhang; Si-Ha A; Li-Juan Yang; Rui Cheng; Hong-Li Li; Guang-Chun Lei (Hydrobiologia, 2023)

Development of a highly sensitive immunoassay based on pentameric nanobodies for carcinoembryonic antigen detection - Yi Gu; Yang Guo; Yang Deng; Haipeng Song; Rui Nian; Wenshuai Liu (Analytica Chimica Acta, 2023)

Farmers’ participation into the recovery of waste agricultural plastic film: An application of the Theory of Planned Behavior - Ze-Ying Zhao; Wen-Bo Li; Peng-Yang Wang; Hong-Yan Tao; Rui Zhou; Jin-Ying Cui; Jian Zhang; Tao Tian; Xu-Zhe Zhao; Yi-Bo Wang; You-Cai Xiong (Waste Management, 2023)

Unraveling the role of unpaired 3d electrons in e orbital of CoO: Driving π feedback of N2 for efficient ammonia electrosynthesis - Yuanyuan Xiong; Liang Zhao; Rui Zhao; Xiaoxuan Wang; Xinyue Chi; Kaixin Zhang; Zhenzhen Fu; Shuyuan Li; Jiaou Wang; Kaiqi Nie; Zhiyu Yang; Yi-Ming Yan (Chemical Engineering Journal, 2023)

Contrasting the effect of aerosol properties on the planetary boundary layer height in Beijing and Nanjing - Xin Huang; Yuying Wang; Yi Shang; Xiaorui Song; Rui Zhang; Yuxiang Wang; Zhanqing Li; Yuanjian Yang (Atmospheric Environment, 2023)

Highly stretchable phase change composites for simultaneous health monitoring and thermotherapy - Yi-Cun Zhou; Jie Yang; Wu-Di Li; Peng Yu; Zheng-Min Zhang; Lu Bai; Rui-Ying Bao; Wei Yang (Chemical Engineering Journal, 2023)

AIWW: a new nutrition-screening tool for the oncologic population - Yi-Zhong Ge; Zhen-Ming Fu; Qi Zhang; Meng-Meng Song; Guo-Tian Ruan; Xi Zhang; Xiao-Wei Zhang; Xiang-Rui Li; Kang-Ping Zhang; Meng Tang; Xiao-Yue Liu; Ming Yang; et al. (Science China Life Sciences, 2023)

Lithium recovery and solvent reuse from electrolyte of spent lithium-ion battery - Rui Xu; Shuya Lei; Tianyu Wang; Chenxing Yi; Wei Sun; Yue Yang (Waste Management, 2023)

Study of infectious hypodermal and hematopoietic necrosis virus (IHHNV) infection in different organs of Penaeus vannamei - Zi-Hao Hou; Yang Gao; Jing-Jing Wang; Cai-Yi Chen; Lin-Rui Chang; Ting Li; Ling-Jun Si; Fan Li; Dong-Chun Yan (Journal of Invertebrate Pathology, 2023)

Plasmon driven super-high HER activity of electronic structure and lattice strain engineered single atomic layer Pd@Au nanorods - Yi-Bai Sun; Miao Ni; Chen Chi; Dong-Rui Yang; Xue-Lu Chen; Qi Qi; Jian Li; Xing-Hua Xia (Chemical Engineering Journal, 2023)

Genetic and Phenotypic Spectrum of Amyotrophic Lateral Sclerosis Patients with CCNF Variants from a Large Chinese Cohort - Bi Zhao; Qirui Jiang; Junyu Lin; Qianqian Wei; Chunyu Li; Yanbing Hou; Bei Cao; Lingyu Zhang; Ruwei Ou; Kuncheng Liu; Tianmi Yang; Yi Xiao; et al. (Molecular Neurobiology, 2023)
Cyclin F (CCNF) variants have been found to be associated with amyotrophic lateral sclerosis (ALS)/frontotemporal dementia (FTD). However, the genetic and clinical characteristics of ALS patients who carry CCNF variants are largely unknown. Genetic analysis was performed for 1587 Chinese ALS patients, and missense variants were predicted by software analyses. Additionally, we searched PubMed, Embase, and Web of Science for relevant literature and conducted a meta-analysis of the frequency of variants. In our ALS cohort, we identified 29 nonsynonymous variants in 41 ALS patients. Among these ALS patients, 18 (1.1%) were carriers of 15 rare missense variants that were considered probably pathogenic variants, and 11 of 15 variants were novel. Seven relevant studies were identified, and a total of 43 CCNF variants in 59 ALS patients with a frequency of 0.8% were reported. The ratio of males to females in our cohort (10/8) was similar to that in Caucasian populations (4/7) and significantly higher than that in Asian populations (10/1). The proportion of bulbar onset in Caucasian CCNF carriers was similar to our cohort (25.0 vs. 27.8%); however, bulbar onset had never been reported in previous Asian studies (0/11). FTD was not found in CCNF carriers in previous Asian studies and our cohort, but it has been reported in a FALS cohort (1/75) of Caucasian individuals. There were some differences in the clinical characteristics among different ethnic ALS populations. More basic scientific studies are needed to elucidate the pathogenic mechanisms and genotype-phenotype associations of CCNF variants.

Euphpepluone S, a new lathyrane diterpenoid with anti-inflammatory activity from Euphorbia peplus L. - Shi-Peng Guan; Ying Yang; Mao Sun; Min Cai; Xue-Xue Pu; Jian-Yi Huang; Ping Yi; Lin Liu; Ming-Rui Yuan; Yuan-Yuan Cheng; Ying-Tong Di (Phytochemistry Letters, 2023)

Can shallow-incorporated organic mulching replace plastic film mulching for irrigated maize production systems in arid environments? - Ze-Ying Zhao; Peng-Yang Wang; Xiao-Bin Xiong; Rui Zhou; Ying Zhu; Yi-Bo Wang; Ning Wang; Kiprotich Wesly; Wei Xue; Jing Cao; Jin-Lin Zhang; Hong-Yan Tao; et al. (Field Crops Research, 2023)

Chemical constituents from Ajuga macrosperma Wall. ex Benth. (Lamiaceae) and their chemotaxonomic significance - Hua-Yi Jiang; Yi-Huan Li; Qian-Ru Zhang; Dan Teng; Ming-Ming Li; Rui Yang; Hong-Ping He (Biochemical Systematics and Ecology, 2023)

Underestimation of biomass burning contribution to PM2.5 due to its chemical degradation based on hourly measurements of organic tracers: A case study in the Yangtze River Delta (YRD) region, China - Qing Li; Kun Zhang; Rui Li; Liumei Yang; Yanan Yi; Zhiqiang Liu; Xiaojuan Zhang; Jialiang Feng; Qiongqiong Wang; Wu Wang; Ling Huang; Yangjun Wang; et al. (Science of The Total Environment, 2023)

Particulate matter capturing over manganese dioxides with different crystal structures - Rui Liu; Huan-Huan Yang; Hao Zhou; Xianliang Yi; Yang Liu (Journal of Environmental Sciences, 2023)

Manipulating electron redistribution of active sites by in situ engineering B-S-V bond in VS2 catalyst for stable nitrogen fixation - Xinyue Chi; Rui Zhao; Xiaoxuan Wang; Yuanyuan Xiong; Kaixin Zhang; Zhenzhen Fu; Yebo Yao; Shuyuan Li; Zhi-Yu Yang; Yi-Ming Yan (Chemical Engineering Journal, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Exogenous methyl jasmonate and cytokinin antagonistically regulate lignin biosynthesis by mediating CsHCT expression in Camellia sinensis - Chun-Fang Liu; Ni Yang; Rui-Min Teng; Jing-Wen Li; Yi Chen; Zhi-Hang Hu; Tong Li; Jing Zhuang (Protoplasma, 2023)

Comparative transcriptomes analysis of the ovary reveals potential ovarian development-related genes and pathways in Macrobrachium rosenbergii - Yan-Hao Yang; Rui Wang; Ming Li; Hui-Zan Yang; Guang-Hua Huang; Ke-Yi Ma; Gao-Feng Qiu; Yong Lin (Invertebrate Reproduction & Development, 2023)

A semi-analytical method for predicting train-induced vibrations considering train-track-soil and soil-pile-building dynamic interactions - Zi-Yu Tao; Chao Zou; Guang-Rui Yang; Yi-Min Wang (Soil Dynamics and Earthquake Engineering, 2023)

Molecular Hydrogen: an Emerging Therapeutic Medical Gas for Brain Disorders - Chongyun Wu; Peibin Zou; Shu Feng; Ling Zhu; Fanghui Li; Timon Cheng-Yi Liu; Rui Duan; Luodan Yang (Molecular Neurobiology, 2023)

Improving VOC control strategies in industrial parks based on emission behavior, environmental effects, and health risks: A case study through atmospheric measurement and emission inventory - Ling Li; Dan Zhang; Wei Hu; Yi Yang; Sidi Zhang; Rui Yuan; Pingjiang Lv; Weidong Zhang; Yong Zhang; Yunhuai Zhang (Science of The Total Environment, 2023)

Two pathways drive enhanced nitrogen acquisition via a complementarity effect in long-term intercropping - Yi Xing; Rui-Peng Yu; Ran An; Ning Yang; Jin-Pu Wu; Huai-Ying Ma; Jiu-Dong Zhang; Xing-Guo Bao; Hans Lambers; Long Li (Field Crops Research, 2023)

Slab dehydration and magmatism in the Kurile arc as a function of depth: An investigation based on B-Sr-Nd-Hf isotopes - Hong-Yan Li; Chao Xie; Jeffrey G. Ryan; Chuan-Mao Yang; Rui-Peng Zhao; Chao Zhang; Yi-Gang Xu (Chemical Geology, 2023)

Vitellogenin accumulation leads to reproductive senescence by impairing lysosomal function - Jie Tang; Yi-Cheng Ma; Yuan-Li Chen; Rui-Qiu Yang; Heng-Chen Liu; Xin Wang; Baosen Ni; Cheng-Gang Zou; Ke-Qin Zhang (Science China Life Sciences, 2023)

Effects of Alpine Grassland Degradation on Soil Microbial Communities in Qilian Mountains of China - Chunming Li; Derong Zhang; Gengchun Xu; Rui Yan; Yang Huang; Liuqing Feng; Jin Yi; Xiangyu Xue; Huixia Liu (Journal of Soil Science and Plant Nutrition, 2023)

Tectonic boundaries in the South China Sea from aeromagnetic signature - Yao Luo; Hang Yin; Qiang Liu; Jingmin Li; Shihua Liu; Wei Gao; Rui Li; Yi Yang (Journal of Oceanology and Limnology, 2023)

Rockburst and microseismic activity in a lagging tunnel as the spacing between twin TBM excavated tunnels changes: A case from the Neelum-Jhelum hydropower project - Peng-Xiang Li; Bing-Rui Chen; Ya-Xun Xiao; Guang-Liang Feng; Yang-Yi Zhou; Jin-Shuai Zhao (Tunnelling and Underground Space Technology, 2023)

In situ degradation of low-density polyethylene film in irrigation maize field: Thickness-dependent effect - Xiao-Bin Xiong; Ze-Ying Zhao; Peng-Yang Wang; Rui Zhou; Jing Cao; Jing Wang; Kiprotich Wesly; Wen-Li Wang; Ning Wang; Meng Hao; Yi-Bo Wang; Hong-Yan Tao; et al. (Science of The Total Environment, 2023)

Evaluations of policy contagion for new energy vehicle industry in China - Cody Yu-Ling Hsiao; Rui Yang; Xin Zheng; Yi-Bin Chiu (Energy Policy, 2023)

TREM2 and Microglia Contribute to the Synaptic Plasticity: from Physiology to Pathology - Chao-Ji Yu; Meng Wang; Rui-Yang Li; Tao Wei; Han-Chen Yang; Yun-Si Yin; Ying-Xin Mi; Qi Qin; Yi Tang (Molecular Neurobiology, 2023)

Upregulation LncRNA MEG3 expression suppresses proliferation and metastasis in melanoma via miR-208/SOX4 - Yi Yang; Liang Jin; Juan He; Rui Wang; Yilin Wang; Jia Bai; Youbai Chen; Zhanpeng Luo (Molecular and Cellular Biochemistry, 2023)

Intercrop overyielding weakened by high inputs: Global meta-analysis with experimental validation - Shuang-Guo Zhu; Hao Zhu; Rui Zhou; Wei Zhang; Wei Wang; Yi-Ning Zhou; Bao-Zhong Wang; Yu-Miao Yang; Jing Wang; Hong-Yan Tao; You-Cai Xiong (Agriculture, Ecosystems & Environment, 2023)

Naïve-like conversion of bovine induced pluripotent stem cells from Sertoli cells - Yu Jiang; Ning-Ning Cai; Xing-Lan An; Wen-Qian Zhu; Rui Yang; Bo Tang; Zi-Yi Li; Xue-Ming Zhang (Theriogenology, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Study on the prepared bio-oil by catalytic hydrothermal liquefaction of antibiotic residues in ethanol-water reaction system with transition metal modified HZSM-5 - Jian Yang; Rui Ma; Yi Xing; Hongzhi Ma; Biqin Dong; Hongxia Li; Chen Hong; Changlei Xia (Fuel, 2023)

A stack-up electrochemical device based on metal-organic framework modified carbon paper for ultra-trace lead and cadmium ions detection - Yue-Hong Pang; Qiu-Yu Yang; Rui Jiang; Yi-Ying Wang; Xiao-Fang Shen (Food Chemistry, 2023)

Phytochemical and underlying mechanism of Mikania micrantha Kunth on antibiotic resistance genes, and pathogenic microbes during chicken manure composting - Yousif Abdelrahman Yousif Abdellah; Yu-Sen Luo; Shan-Shan Sun; Xi Yang; Hong-Yi Ji; Rui-Long Wang (Bioresource Technology, 2023)

Efficacy and Safety of Recombinant Human Prourokinase in Acute Ischemic Stroke: A Phase IIa Randomized Clinical Trial - Haiqing Song; Yuan Wang; Qingfeng Ma; Huisheng Chen; Bo Liu; Yi Yang; Jianguo Zhu; Shigang Zhao; Xiaoping Jin; Yongqiu Li; Yanyong Wang; Runxiu Zhu; et al. (Translational Stroke Research, 2022)

An improved bicubic imaging fitting algorithm for 3D radar detection target - Fan-Ruo Li; Feng Yang; Rui Yan; Qiao Xu; Yi-Jin Li; Hong-Jia Xing (Applied Geophysics, 2022)

Root morphology and physiology responses of two subtropical tree species to NH4+-N and NO3−-N deposition in phosphorus-barren soil - Rui Zhang; Zhongyi Yang; Yunpeng Wang; Jiayi Wang; Yi Wang; Zhichun Zhou (New Forests, 2022)

Surfactin isoforms isolated from a mushroom derived Bacillus halotolerans DMG-7-2 - Guo-Feng Zhou; Lin Yang; Shu-Hua Zhang; Yi Wang; Yu Yang; Rui Xu; Xue Zhao; Dan Nie; Junjie Shan; Cheng-Bin Cui; Chang-Wei Li (Natural Product Research, 2022)

Evaluation of Port–Hinterland Synergy Level Considering Fixed Asset Allocation and Social Commodity Circulation under the “Dual Circulation” Development Pattern - Zhaohui Li; Yujin Huang; Fan Yang; Yi Li; Yan Fang; Rui Fu (Journal of Marine Science and Engineering, 2022)
“Port–hinterland synergy” means the development of port and hinterland should promote each other. The “dual circulation” development pattern indicates the requirement of exploring the domestic transportation demand and promoting the integration between ports and hinterlands. However, the current research on the synergy level between ports and hinterlands is not enough to meet the needs of constructing a “dual circulation” development pattern, and few studies have explored the influencing factors of port–hinterland synergy level directly, especially in the context of the new development pattern of “dual circulation”. After investigating the synergetic mechanism between ports and hinterlands, this study proposes to further consider the influence of fixed assets allocation and social commodity circulation on the synergy level under the “dual circulation” pattern. So, fixed asset investment and three different forms of commodity circulation activities are selected to represent the corresponding hinterland’s economic activities and added into the evaluation indices. To assess ports’ responsiveness to different kinds of transport demand, throughputs of each port are divided into those of domestic and foreign countries. Then this paper evaluates the level of port–hinterland synergy by the coupling synergy model, and the influence degree of these activities on the synergy level was studied with the partial least squares regression (PLS). The results show that there is heterogeneity in regional and port positioning in the port–hinterland synergy level, and that four selected economic activities’ improvement can enhance the port–hinterland synergy level. Among them, retail industry has the strongest positive effect, followed by tertiary industry, import and export trade, and fixed asset investment.

Isolation and Analysis of Reverse Transcriptase of Ty1-copia-Like Retrotransposons in Sugarcane - Jun-Xian Liu; Jing Liu; Tai-Yi Yang; Li-Min Liu; Li-Hang Qiu; Yi-Jing Gao; Wei-Xing Duan; Jing-Chao Lei; Hong-Jian Liu; Rong-Hua Zhang; Wei-Zhong He; Song Li; et al. (Sugar Tech, 2022)

Clinical profiles and antimicrobial resistance patterns of invasive Salmonella infections in children in China - Wen Song; Qingwen Shan; Yue Qiu; Xianyao Lin; Chunhui Zhu; Zhiqiang Zhuo; Caihong Wang; Jianning Tong; Rui Li; Chaomin Wan; Yu Zhu; Minxia Chen; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2022)
Invasive Salmonella infections result in a significant burden of disease including morbidity, mortality, and financial cost in many countries. Besides typhoid fever, the clinical impact of non-typhoid Salmonella infections is increasingly recognized with the improvement of laboratory detection capacity and techniques. A retrospective multicenter study was conducted to analyze the clinical profiles and antimicrobial resistance patterns of invasive Salmonella infections in hospitalized children in China during 2016–2018. A total of 130 children with invasive Salmonella infections were included with the median age of 12 months (range: 1–144 months). Seventy-nine percent of cases occurred between May and October. Pneumonia was the most common comorbidity in 33 (25.4%) patients. Meningitis and septic arthritis caused by nontyphoidal Salmonella (NTS) infections occurred in 12 (9.2%) patients and 5 (3.8%) patients. Patients < 12 months (OR: 16.04) and with septic shock (OR: 23.4), vomit (OR: 13.33), convulsion (OR: 15.86), C-reactive protein (CRP) ≥ 40 g/L (OR: 5.56), and a higher level of procalcitonin (PCT) (OR: 1.05) on admission were statistically associated to an increased risk of developing meningitis. Compared to 114 patients with NTS infections , 16 patients with typhoid fever presented with higher levels of CRP and PCT ( P < 0.05). The rates of resistance to ampicillin, sulfamethoxazole/trimethoprim, ciprofloxacin, and ceftriaxone among Salmonella Typhi and NTS isolates were 50% vs 57.3%, 9.1% vs 24.8%, 0% vs 11.2%, and 0% vs 9.9%, respectively. NTS has been the major cause of invasive Salmonella infections in Chinese children and can result in severe diseases. Antimicrobial resistance among NTS was more common.

Genotypic variations in GST genes reveal a regulatory role in the accumulation of caffeoylquinic acids in leafy sweet potato (Ipomoea batatas) - Deka Reine Judesse Soviguidi; Yi Liu; Rui Pan; Salah Fatouh Abou-Elwafa; Wen-Ying Zhang; Xin-Sun Yang (Plant Cell, Tissue and Organ Culture (PCTOC), 2022)

miR-517b-3p promotes the progression of portal vein tumor thrombus via activating Wnt/β-catenin signaling pathway in hepatocellular carcinoma - Rui-Sheng Ke; Kun-Zhai Huang; De-sheng Bao; Jing-Rui Yang; Hua-xiang Wang; Li-Zhi Lv; Yi Jiang; Zhao-Hui Liu; Fu-Xing Zhang (Molecular Biology Reports, 2022)

Metatranscriptomic analysis of host response and vaginal microbiome of patients with severe COVID-19 - Meng Xiao; Bo Lu; Rui Ding; Xia Liu; Xian Wu; Yaqian Li; Xudong Liu; Lin Qiu; Zhibo Zhang; Jing Xie; Yu Chen; Dong Zhang; et al. (Science China Life Sciences, 2022)

Belowground processes and sustainability in agroecosystems with intercropping - Rui-Peng Yu; Hao Yang; Yi Xing; Wei-Ping Zhang; Hans Lambers; Long Li (Plant and Soil, 2022)

Extracellular vesicles derived from human Sertoli cells: characterizations, proteomic analysis, and miRNA profiling - Xiao-Hui Tan; Sheng-Ji Gu; Wen-Jie Tian; Wen-Peng Song; Yang-Yang Gu; Yi-Ming Yuan; Xue-Song Li; Zhong-Cheng Xin; Sae Woong Kim; Rui-Li Guan; Woong Jin Bae (Molecular Biology Reports, 2022)

Two new cytotoxic cycloartane triterpenoids from Aphanamixis polystachya (Wall.) R. N. Parker - Yi-ting Wang; Shi-rui Fan; Jie-yun Cai; Jing-jing Guo; Xin-fang Zhang; Bi-juan Yang; Xiao-jiang Hao; Duo-zhi Chen (Natural Product Research, 2022)

Identification of PDXDC1 as a novel pleiotropic susceptibility locus shared between lumbar spine bone mineral density and birth weight - Yu-Qian Song; Shi-Di Hu; Xu Lin; Xiang-He Meng; Xiao Wang; Yin-Hua Zhang; Cheng Peng; Rui Gong; Tao Xu; Tong Zhang; Chen-Zhong Li; Dao-Yan Pan; et al. (Journal of Molecular Medicine, 2022)
An increasing number of epidemiological studies have suggested that birth weight (BW) may be a determinant of bone health later in life, although the underlying genetic mechanism remains unclear. Here, we applied a pleiotropic conditional false discovery rate (cFDR) approach to the genome-wide association study (GWAS) summary statistics for lumbar spine bone mineral density (LS BMD) and BW, aiming to identify novel susceptibility variants shared between these two traits. We detected 5 novel potential pleiotropic loci which are located at or near 7 different genes ( NTAN1 , PDXDC1 , CACNA1G , JAG1 , FAT1P1 , CCDC170 , ESR1 ), among which PDXDC1 and FAT1P1 have not previously been linked to these phenotypes. To partially validate the findings, we demonstrated that the expression of PDXDC1 was dramatically reduced in ovariectomized (OVX) mice in comparison with sham-operated (SHAM) mice in both the growth plate and trabecula bone. Furthermore, immunohistochemistry assay with serial sections showed that both osteoclasts and osteoblasts express PDXDC1 , supporting its potential role in bone metabolism. In conclusion, our study provides insights into some shared genetic mechanisms for BMD and BW as well as a novel potential therapeutic target for the prevention of OP in the early stages of the disease development. Key messages We investigated pleiotropy-informed enrichment between LS BMD and BW. We identified genetic variants related to both LS BMD and BW by utilizing a cFDR approach. PDXDC1 is a novel pleiotropic gene which may be related to both LS BMD and BW. Elevated expression of PDXDC1 is related to higher BMD and lower ratio n-6/n-3 PUFA indicating a bone protective effect of PDXDC1.

Flavonoid glycosides from the nectar of Camellia reticulata Lindl. - Xin-Lan Chen; Xing-Rong Peng; Xue-Yang Gong; Yi-Qiu Liu; Zhuo Qing; Xiao-Xiao Ren; Rui Su; Li-Ming Fang; Ming-Hua Qiu; Kun Dong (Natural Product Research, 2022)

Chrysomutanin and related meroterpenoids from a DES mutant of the marine-derived fungus Penicillium chrysogenum S-3-25 - Hua Qiao; Shu-Hua Zhang; Yuan Dong; Yu Yang; Rui Xu; Bo Chen; Yi Wang; Tian-Jiao Zhu; Cheng-Bin Cui; Guo-Gang Zhang; Chang-Wei Li (Natural Product Research, 2022)

Functional characterization of tyrosine decarboxylase genes that contribute to acteoside biosynthesis in Rehmannia glutinosa - Yan Hui Yang; Mu Rong Yang; Jian Yu Zhu; Ke Wei Dong; Yan Jie Yi; Rui Fang Li; Lei Zeng; Chang Fu Zhang (Planta, 2022)

Microglial SIRPα Deletion Facilitates Synapse Loss in Preclinical Models of Neurodegeneration - Chongyun Wu; Luodan Yang; Hannah Youngblood; Timon Cheng-Yi Liu; Rui Duan (Neuroscience Bulletin, 2022)

miR-181b-5p Promotes the Progression of Cholangiocarcinoma by Targeting PARK2 via PTEN/PI3K/AKT Signaling Pathway - Zhe-Long Jiang; Fu-Xing Zhang; Hong-Liang Zhan; He-Jun Yang; Si-Yu Zhang; Zhao-Hui Liu; Yi Jiang; Li-Zhi Lv; Rui-Sheng Ke (Biochemical Genetics, 2022)

A New Instrumental Array in Sichuan, China, to Monitor Vibrations and Perturbations of the Lithosphere, Atmosphere, and Ionosphere - Chieh-Hung Chen; Yang-Yi Sun; Kai Lin; Chen Zhou; Rui Xu; Haiyin Qing; Yongxin Gao; Tao Chen; Fei Wang; Huaizhong Yu; Peng Han; Chi-Chia Tang; et al. (Surveys in Geophysics, 2021)

Elevated pCO2 Impedes Succession of Phytoplankton Community From Diatoms to Dinoflagellates Along With Increased Abundance of Viruses and Bacteria - Ruiping Huang; Jiazhen Sun; Yunlan Yang; Xiaowen Jiang; Zhen Wang; Xue Song; Tifeng Wang; Di Zhang; He Li; Xiangqi Yi; Shouchang Chen; Nanou Bao; et al. (Frontiers in Marine Science, 2021)
Eutrophic coastal regions are highly productive and greatly influenced by human activities. Primary production supporting the coastal ecosystems is supposed to be affected by progressive ocean acidification driven by increasing CO 2 emissions. In order to investigate the effects of high p CO 2 (HC) on eutrophic plankton community structure and ecological functions, we employed 9 mesocosms and carried out an experiment under ambient (∼410 ppmv) and future high (1000 ppmv) atmospheric p CO 2 conditions, using in situ plankton community in Wuyuan Bay, East China Sea. Our results showed that HC along with natural seawater temperature rise significantly boosted biomass of diatoms with decreased abundance of dinoflagellates in the late stage of the experiment, demonstrating that HC repressed the succession from diatoms to dinoflagellates, a phenomenon observed during algal blooms in the East China Sea. HC did not significantly influence the primary production or biogenic silica contents of the phytoplankton assemblages. However, the HC treatments increased the abundance of viruses and heterotrophic bacteria, reflecting a refueling of nutrients for phytoplankton growth from virus-mediated cell lysis and bacterial degradation of organic matters. Conclusively, our results suggest that increasing CO 2 concentrations can modulate plankton structure including the succession of phytoplankton community and the abundance of viruses and bacteria in eutrophic coastal waters, which may lead to altered biogeochemical cycles of carbon and nutrients.

Phase field model for hydraulic fracture propagation in porous medium and numerical simulation analysis of hydraulic fracture propagation in a layered reservoir - Liang-Ping Yi; Chang-Xin Yang; Rui Chen; Jing-Yi Zhu; Xiao-Hua Zhu; Zhao-Zhong Yang; Xiao-Gang Li (Arabian Journal of Geosciences, 2021)

Genome sequencing and functional annotation of Bacillus sp. strain BS-Z15 isolated from cotton rhizosphere soil having antagonistic activity against Verticillium dahliae - Zhong-Yi Chen; Xieerwanimu Abuduaini; Nuramina Mamat; Qi-Lin Yang; Meng-Jun Wu; Xin-Rui Lin; Ru Wang; Rong-Rong Lin; Wei-Jun Zeng; Huan-Chen Ning; He-Ping Zhao; Jin-Yu Li; et al. (Archives of Microbiology, 2021)

A novel role of the mitochondrial iron-sulfur cluster assembly protein ISCU-1/ISCU in longevity and stress response - Yi Sheng; Guang Yang; Kaitlyn Casey; Shayla Curry; Mason Oliver; Sung Min Han; Christiaan Leeuwenburgh; Rui Xiao (GeroScience, 2021)

Microbiological profiles and antimicrobial resistance patterns of pediatric bloodstream pathogens in China, 2016–2018 - Yue Qiu; Junwen Yang; Yiping Chen; Jinhong Yang; Qingxiong Zhu; Chunhui Zhu; Shuangjie Li; Jing Liu; Chaomin Wan; Yu Zhu; Minxia Chen; Yi Xu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

A novel method for extraction of polypropylene microplastics in swine manure - Rui-Ting Wu; Ying-Feng Cai; Si-Cheng Xing; Yi-Wen Yang; Jian-Dui Mi; Xin-Di Liao (Environmental Science and Pollution Research, 2021)

Protective equipment and health education program could benefit students from dust pollution - Yi-Chen Chiang; Xian Li; Chun-Yang Lee; Jia Rui; Chiung-Wen Hu; Hao-Jan Yang; Szu-Chieh Chen; Tianmu Chen; Yanhua Su; Chung-Yih Kuo; Shao-Chieh Hsueh (Air Quality, Atmosphere & Health, 2021)

Small RNA Sequencing Analysis of Germinating Single-bud Seedcane Sett in Sugarcane - Kai-Chao Wu; Lin Xu; Zhi-Nian Deng; Tian Pang; Rong-Hua Zhang; Yi-Jie Li; Xiao-Yan Liu; Cheng-Feng Huang; Wen-Xian Qin; Jian-Feng Wei; Li-Ping Wei; Yang-Rui Li; et al. (Sugar Tech, 2021)

Astrocyte-Derived Lactate Modulates the Passive Coping Response to Behavioral Challenge in Male Mice - Ya-Nan Yin; Jian Hu; Yi-Li Wei; Ze-Lin Li; Zhou-Cai Luo; Rui-Qi Wang; Ke-Xin Yang; Shu-Ji Li; Xiao-Wen Li; Jian-Ming Yang; Tian-Ming Gao (Neuroscience Bulletin, 2021)

Two new bioactive lignans from leaves and twigs of Cleistanthus concinnus Croizat - Shi-rui Fan; Jing-jing Guo; Yi-ting Wang; Bi-juan Yang; Duo-zhi Chen; Xiao-jiang Hao (Natural Product Research, 2020)

Characterization of a Cu2+, SDS, alcohol and glucose tolerant GH1 β-glucosidase from Bacillus sp. CGMCC 1.16541 - Yi-Rui Yin; Peng Sang; Feng-Li Yang; Tao Li; Run-Feng Yang; Hong-Yan Liu; Zong-Long Luo; Wen-Jun Li; Li-Quan Yang (Antonie van Leeuwenhoek, 2020)

A bacterial polysaccharide biosynthesis-related gene inversely regulates larval settlement and metamorphosis of Mytilus coruscus - Li-Hua Peng; Xiao Liang; Rui-Heng Chang; Jia-Yi Mu; Hui-E Chen; Asami Yoshida; Kiyoshi Osatomi; Jin-Long Yang (Biofouling, 2020)

Interferon-α2b spray inhalation did not shorten virus shedding time of SARS-CoV-2 in hospitalized patients: a preliminary matched case-control study - Shao-rui Hao; Ren Yan; Shan-yan Zhang; Jiang-shan Lian; Huan Cai; Xiao-li Zhang; Lin Zheng; Hong-yu Jia; Jian-hua Hu; Guo-dong Yu; Jue-qing Gu; Chan-yuan Ye; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

BTBD9 and dopaminergic dysfunction in the pathogenesis of restless legs syndrome - Shangru Lyu; Atbin Doroodchi; Hong Xing; Yi Sheng; Mark P. DeAndrade; Youfeng Yang; Tracy L. Johnson; Stefan Clemens; Fumiaki Yokoi; Michael A. Miller; Rui Xiao; Yuqing Li (Brain Structure and Function, 2020)

Salvianolic acid A attenuated myocardial infarction–induced apoptosis and inflammation by activating Trx - Rui Zhou; Jinhuan Gao; Changpei Xiang; Zhenming Liu; Yi Zhang; Jingjing Zhang; Hongjun Yang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

Lactate accelerates vascular calcification through NR4A1-regulated mitochondrial fission and BNIP3-related mitophagy - Yi Zhu; Xi-Qiong Han; Xue-Jiao Sun; Rui Yang; Wen-Qi Ma; Nai-Feng Liu (Apoptosis, 2020)

Anti-phytopathogenic Bacterial Metabolites From the Seaweed-Derived Fungus Aspergillus sp. D40 - Rui-Huan Huang; Wei Lin; Peng Zhang; Jian-Yang Liu; Dan Wang; Yi-Qiang Li; Xiao-Qiang Wang; Cheng-Sheng Zhang; Wei Li; Dong-Lin Zhao (Frontiers in Marine Science, 2020)

Comparison of epidemiological and clinical characteristics of COVID-19 patients with and without Wuhan exposure - Jiang-shan Lian; Huan Cai; Shao-rui Hao; Xi Jin; Xiao-li Zhang; Lin Zheng; Hong-yu Jia; Jian-hua Hu; Shan-yan Zhang; Guo-dong Yu; Jue-qing Gu; Chan-yuan Ye; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

Enhancement of the summer extreme precipitation over North China by interactions between moisture convergence and topographic settings - Yang Zhao; Deliang Chen; Jiao Li; Dandan Chen; Yi Chang; Juan Li; Rui Qin (Climate Dynamics, 2020)
This study investigates the roles of atmospheric moisture transport under the influence of topography for summer extreme precipitation over North China (NC) during 1979–2016. Based on rain gauge precipitation data and a reanalysis, 38 extreme precipitation days in NC during the 38 years were selected and associated moisture fluxes estimated. The results show that there is a dominant moisture influx of 311.8 kg m −1 s −1 into NC along its southern boundary from tropical oceans, and a secondary influx of 107.9 kg m −1 s −1 across its western boundary carried by mid-latitude westerlies. The outflux across the eastern boundary is 206.9 kg m −1 s −1 and across the northern boundary is 76.0 kg m −1 s −1 , giving a net moisture gain over NC of 136.8 kg m −1 s −1 . During extreme precipitation days, the moisture flux convergence (MFC) was much larger, exceeding 4 × 10 −5 kg m −1 s −1 . The MFC maximum core, the pronounced moisture transport, and the striking extreme precipitation zone over NC are all anchored to the east of the steep slopes of the surrounding topography. Moreover, a remarkably high humidity and strong upward motion also occur near steep slopes, indicating the critical role of the adjacent topography on the extreme precipitations. Simulations with and without the topography in NC using the Weather and Research Forecasting model for six selected out of the 38 extreme precipitation days demonstrate that the surrounding topography reinforces the MFC over NC by 16% relative to the case without terrain, primarily through enhanced wind convergence and higher moisture content, as well as stronger vertical motion induced by diabatic heating. The interactions between moisture convergence and topographic settings strengthen the extreme precipitation over NC.

De novo assembly and transcriptome analysis of differentially expressed genes relevant to variegation in hawthorn flowers - Wei Ji; Wei Zhao; Rong-Chen Liu; Xiao-Bo Jiao; Kai Han; Zhong-Yi Yang; Mei-Ying Gao; Rui Ren; Xiu-Juan Fan; Ming-Xia Yang (Plant Biotechnology Reports, 2019)

Analysis and Simulation of the Stratospheric Quasi-zero Wind Layer over Korla, Xinjiang Province, China - Rui Yang; Lingkun Ran; Yuli Zhang; Yi Liu (Advances in Atmospheric Sciences, 2019)

Intraseasonal Oscillation of Tropospheric Ozone over the Indian Summer Monsoon Region - Yuli Zhang; Chuanxi Liu; Yi Liu; Rui Yang (Advances in Atmospheric Sciences, 2019)

Association Between Body Mass Index and Disease Severity in Chinese Spinocerebellar Ataxia Type 3 Patients - Jin-Shan Yang; Ping-Ping Chen; Min-Ting Lin; Mei-Zhen Qian; Hui-Xia Lin; Xiao-Ping Chen; Xian-Jin Shang; Dan-Ni Wang; Yu-Chao Chen; Bin Jiang; Yi-Jun Chen; Ning Wang; et al. (The Cerebellum, 2018)

Low dosage of arsenic trioxide (As2O3) inhibits angiogenesis in epithelial ovarian cancer without cell apoptosis - Dehong Luo; Xiaoyuan Zhang; Renle Du; Wenjuan Gao; Na Luo; Shuangtao Zhao; Yi Li; Rui Chen; Hui Wang; Yonghua Bao; Wancai Yang; Daishun Liu; et al. (JBIC Journal of Biological Inorganic Chemistry, 2018)

Clinical characteristics and mutation analysis of five Chinese patients with maple syrup urine disease - Xiaomei Li; Yali Yang; Qing Gao; Min Gao; Yvqiang Lv; Rui Dong; Yi Liu; Kaihui Zhang; Zhongtao Gai (Metabolic Brain Disease, 2018)

The root transcriptome of Achyranthes bidentata and the identification of the genes involved in the replanting benefit - Yan Hui Yang; Ming Jie Li; Yan Jie Yi; Rui Fang Li; Cheng Dong; Zhong Yi Zhang (Plant Cell Reports, 2018)

Spatial trends and pollution assessment for mercury in the surface soils of the Nansi Lake catchment, China - Ming-Yi Ren; Li-Yuan Yang; Long-Feng Wang; Xue-mei Han; Jie-Rui Dai; Xu-Gui Pang (Environmental Science and Pollution Research, 2018)

Mechanisms of Acupuncture Therapy for Cerebral Ischemia: an Evidence-Based Review of Clinical and Animal Studies on Cerebral Ischemia - Wen Zhu; Yang Ye; Yi Liu; Xue-Rui Wang; Guang-Xia Shi; Shuai Zhang; Cun-Zhi Liu (Journal of Neuroimmune Pharmacology, 2017)

Structural Transformation Detection Contributes to Screening of Behaviorally Active Compounds: Dynamic Binding Process Analysis of DhelOBP21 from Dastarcus helophoroides - Rui-Nan Yang; Dong-Zhen Li; Guangqiang Yu; Shan-Cheng Yi; Yinan Zhang; De-Xin Kong; Man-Qun Wang (Journal of Chemical Ecology, 2017)

Creation of miniature pig model of human Waardenburg syndrome type 2A by ENU mutagenesis - Tang Hai; Weiwei Guo; Jing Yao; Chunwei Cao; Ailing Luo; Meng Qi; Xianlong Wang; Xiao Wang; Jiaojiao Huang; Ying Zhang; Hongyong Zhang; Dayu Wang; et al. (Human Genetics, 2017)

ATP-Citrate Lyase Gene (SoACLA-1), a Novel ACLA Gene in Sugarcane, and Its Overexpression Enhance Drought Tolerance of Transgenic Tobacco - Thi-Thu Phan; Jian Li; Bo Sun; Jia-Yi Liu; Wen-Hui Zhao; Chan Huang; Li-Tao Yang; Yang-Rui Li (Sugar Tech, 2017)

Involvement of FMRP in Primary MicroRNA Processing via Enhancing Drosha Translation - Rui-Ping Wan; Lin-Tao Zhou; Hai-Xuan Yang; Yong-Ting Zhou; Shun-Hua Ye; Qi-Hua Zhao; Mei-Mei Gao; Wei-Ping Liao; Yong-Hong Yi; Yue-Sheng Long (Molecular Neurobiology, 2017)

Role of the SPS Gene Families in the Regulation of Sucrose Accumulation in Sugarcane - Dong-Liang Huang; Cui-Xian Qin; Yi-Yun Gui; Li-Han Zhao; Zhong-Liang Chen; Miao Wang; Yue Sun; Qing Liao; Yang-Rui Li; Prakash Lakshmanan (Sugar Tech, 2017)

Boreal winter Arctic Oscillation as an indicator of summer SST anomalies over the western tropical Indian Ocean - Dao-Yi Gong; Dong Guo; Yongqi Gao; Jing Yang; Rui Mao; Jingxuan Qu; Miaoni Gao; Sang Li; Seong-Joong Kim (Climate Dynamics, 2017)

Characterization of a neutral recombinant xylanase from Thermoactinospora rubra YIM 77501T - Yi-Rui Yin; Qing-Wen Hu; Wen-Dong Xian; Feng Zhang; En-Min Zhou; Hong Ming; Min Xiao; Xiao-Yang Zhi; Wen-Jun Li (Antonie van Leeuwenhoek, 2017)

Abnormal O-GlcNAcylation of Pax3 Occurring from Hyperglycemia-Induced Neural Tube Defects Is Ameliorated by Carnosine But Not Folic Acid in Chicken Embryos - Rui-Rong Tan; Yi-Fang Li; Shi-Jie Zhang; Wen-Shan Huang; Bun Tsoi; Dan Hu; Xin Wan; Xuesong Yang; Qi Wang; Hiroshi Kurihara; Rong-Rong He (Molecular Neurobiology, 2017)

Spatial distribution of soil cadmium and its influencing factors in peri-urban farmland: a case study in the Jingyang District, Sichuan, China - Bing Li; Rui Xiao; Changquan Wang; Linhai Cao; Yi Zhang; Shunqiang Zheng; Lan Yang; Yong Guo (Environmental Monitoring and Assessment, 2017)

Evaluation of serum immunoglobulins concentrations and distributions in vitiligo patients - Yulong Li; Min Yang; Rui Zhang; Wan Liu; Kuo Zhang; Wei Wen; Lang Yi; Qiaoxian Wang; Mingju Hao; Hui Yang; Jianmin Chang; Jinming Li (Immunologic Research, 2016)

Efficacy of Bt maize producing the Cry1Ac protein against two important pests of corn in China - Hong-Xing Chen; Rui Yang; Wang Yang; Liu Zhang; Ibrahima Camara; Xue-Hui Dong; Yi -Qing Liu; Wang-Peng Shi (Environmental Science and Pollution Research, 2016)

New alkaloids from the leaves of Evodia rutaecarpa - Xiao Xia; Jian-Guang Luo; Rui-Huan Liu; Ming-Hua Yang; Ling-Yi Kong (Natural Product Research, 2016)

Transcriptome of High-Sucrose Sugarcane Variety GT35 - Dong-Liang Huang; Yi-Jing Gao; Yi-Yun Gui; Zhong-Liang Chen; Cui-Xian Qin; Miao Wang; Qing Liao; Li-Tao Yang; Yang-Rui Li (Sugar Tech, 2016)

Cloning and molecular characterization of Myb transcription factors from Leymus (Poaceae: Trticeae) - Ying-xia Lei; Yan Zhang; Yang-yi Li; Jian-Jun Lai; Gang Gao; Hai-qin Zhang; Yong-hong Zhou; Rui-wu Yang (Biologia, 2016)

Molecular Design, Structural Analysis and Antifungal Activity of Derivatives of Peptide CGA-N46 - Rui-Fang Li; Zhi-Fang Lu; Ya-Nan Sun; Shi-Hua Chen; Yan-Jie Yi; Hui-Ru Zhang; Shuo-Ye Yang; Guang-Hai Yu; Liang Huang; Chao-Nan Li (Interdisciplinary Sciences: Computational Life Sciences, 2016)

Application of TiO2-organobentonite modified by cetyltrimethylammonium chloride photocatalyst and polyaluminum chloride coagulant for pretreatment of aging landfill leachate - Yi-Jie Zhang; Zhao-Hui Yang; Pei-Pei Song; Hai-Yin Xu; Rui Xu; Jing Huang; Juan Li; Yan Zhou (Environmental Science and Pollution Research, 2016)

Molecular cloning and characterization of the MsHSP17.7 gene from Medicago sativa L. - Zhen-yi Li; Rui-cai Long; Tie-jun Zhang; Qing-chuan Yang; Jun-mei Kang (Molecular Biology Reports, 2016)

Current approaches to reduce or eliminate mitochondrial DNA mutations - Liang Yang; Tingfang Mei; Xiaobing Lin; Haite Tang; Yi Wu; Rui Wang; Jinglei Liu; Zahir Shah; Xingguo Liu (Science China Life Sciences, 2016)

Isolation and Expression Analysis of Sucrose Synthase Gene (ScSuSy4) from Sugarcane - Zhong-Liang Chen; Yi-Yun Gui; Cui-Xian Qin; Miao Wang; Qing Liao; Dong-Liang Huang; Yang-Rui Li (Sugar Tech, 2016)

Oral administration of Anabaena-expressed VP28 for both drug and food against white spot syndrome virus in shrimp - Xiao-Hui Jia; Chun-Li Zhang; Ding-Ji Shi; Min-Min Zhuang; Xiang Wang; Rui Jia; Zheng-Yang Zhang; Jie Huang; Yi-Hua Sun; Wen-Yi Qian; Guo-Hong Peng; Pei-Min He (Journal of Applied Phycology, 2016)

Phylogenetic analysis of Leymus (Poaceae: Triticeae) based on Random Amplified Polymorphic DNA - Yang-Yi Li; Ying-Xia Lei; Guan-Hui Chai; Gang Gao; Jia-Bin Deng; Yan Zhang; Shan-Shan Tong; Chun-Bang Ding; Li Zhang; Yong-Hong Zhou; Rui-Wu Yang (Biologia, 2016)

Long-Term Effectiveness of Total Hip Replacement with the Collum Femoris Preserving Prosthesis - Rui-jin You; Wen-zhong Zheng; Kun Chen; Hong-sheng Lv; Dian-feng Huang; Yi-zeng Xiao; De-yu Yang; Zhai-quan Su (Cell Biochemistry and Biophysics, 2015)

Historical development and future perspectives of Environmental Specimen Bank in China: a mini review - Fang Qiu; Xiang-Zhou Meng; Yan-Ling Qiu; Qing-Hui Huang; Ying Liu; Ling-Ling Wu; Qian-Fen Xiao; Ya-Jie Sun; Rui Wang; Yi-Hui Zhou; Zhen-Yang Yu; Da-Qiang Yin; et al. (Environmental Science and Pollution Research, 2015)

Weighted species sensitivity distribution method to derive site-specific quality criteria for copper in Tai Lake, China - Rui Shi; Chunhui Yang; Runhua Su; Jiarui Jin; Yi Chen; Hongling Liu; John P. Giesy; Hongxia Yu (Environmental Science and Pollution Research, 2014)

ORF005L from infectious spleen and kidney necrosis virus is located in the inner mitochondrial membrane and induces apoptosis - Rui Wang; Yang Yi; Lihong Liu; Yanghong Lu; Shaoping Weng; Jianguo He; Xiaopeng Xu (Virus Genes, 2014)

The metabolism of 8-heptadecene in Pyropia (Bangiaceae, Rhodophyta) - Min Zhang; Rui-Xia Li; Chuan-Ming Hu; Li-En Yang; Jun Tang; Qin-Qin Lu; Tao Zhang; Zong-Gen Shen; Song-Dong Shen; Pu Xu; Jian-Yi Zhu (Journal of Applied Phycology, 2014)

Interannual linkage between Arctic/North Atlantic Oscillation and tropical Indian Ocean precipitation during boreal winter - Dao-Yi Gong; Yongqi Gao; Dong Guo; Rui Mao; Jing Yang; Miao Hu; Miaoni Gao (Climate Dynamics, 2014)

Constructing genetic linkage maps for Pinus elliottii var. elliottii and Pinus caribaea var. hondurensis using SRAP, SSR, EST and ISSR markers - Hui-xiao Yang; Rui Luo; Fen-cheng Zhao; Tian-yi Liu; Chun-xin Liu; Shao-wei Huang (Trees, 2013)

The Effect of Energy Substrates on PHB Accumulation of Acidiphilium cryptum DX1-1 - Ai-ling Xu; Jin-lan Xia; Zhi-wen Song; Peng Jiang; Yan Xia; Min-xi Wan; Rui-yong Zhang; Yi Yang; Ke-ke Liu (Current Microbiology, 2013)

Effects of Sub-soil Drip Fertigation on Sugarcane in Field Conditions - Gui-Fen Chen; Qi-Zhan Tang; Yang-Rui Li; Yu-Yi Huang; Bin Liu; Lin Xu; Hai-Rong Huang (Sugar Tech, 2012)

Polymorphisms in the XPG gene and risk of gastric cancer in Chinese populations - Jing He; Li-Xin Qiu; Meng-Yun Wang; Rui-Xi Hua; Ruo-Xin Zhang; Hong-Ping Yu; Ya-Nong Wang; Meng-Hong Sun; Xiao-Yan Zhou; Ya-Jun Yang; Jiu-Cun Wang; Li Jin; et al. (Human Genetics, 2012)

Distinct species or colour polymorphism? Life history, morphology and sequence data separate two Pyrrhalta elm beetles (Coleoptera: Chrysomelidae) - Rui-E Nie; Huai-Jun Xue; Yi Hua; Xing-Ke Yang; Alfried P. Vogler (Systematics and Biodiversity, 2012)

Characterization of the expression profiles of calpastatin (CAST) gene in chicken - Zeng-Rong Zhang; Xiao-Song Jiang; Hua-Rui Du; Qing Zhu; Xiao-Cheng Li; Chao-Wu Yang; Yi-Ping Liu (Molecular Biology Reports, 2012)

MicroRNA-17 post-transcriptionally regulates polycystic kidney disease-2 gene and promotes cell proliferation - Huan Sun; Qing-Wei Li; Xiao-Yan Lv; Jian-Zhong Ai; Qiu-Tan Yang; Jing-Jing Duan; Guo-Hui Bian; Yan Xiao; Yi-Dong Wang; Zheng Zhang; Yu-Hang Liu; Rui-Zhi Tan; et al. (Molecular Biology Reports, 2010)

Down-regulation of Pkd2 by siRNAs suppresses cell–cell adhesion in the mouse melanoma cells - Guo-Hui Bian; Ge Cao; Xiao-Yan Lv; Qing-Wei Li; Huan Sun; Yan Xiao; Jian-Zhong Ai; Qui-Tan Yang; Jing-Jing Duan; Yi-Dong Wang; Zheng Zhang; Rui-Zhi Tan; et al. (Molecular Biology Reports, 2010)

Involvement of the ornithine decarboxylase/polyamine system in precondition-induced cardioprotection through an interaction with PKC in rat hearts - Ya-Jun Zhao; Wei-Hua Zhang; Chang-Qing Xu; Hong-Zhu Li; Li-Na Wang; Hong Li; Yi-Hua Sun; Yan Lin; Li-Ping Han; Li Zhang; Yie Tian; Rui Wang; et al. (Molecular and Cellular Biochemistry, 2009)

Quantification of Three Key Enzymes Involved in Artemisinin Biogenesis in Artemisia annua by Polyclonal Antisera-Based ELISA - Qing-Ping Zeng; Xiao-Mei Zeng; Lu-Lu Yin; Rui-Yi Yang; Li-Ling Feng; Xue-Qin Yang (Plant Molecular Biology Reporter, 2009)

Vesicular stomatitis virus matrix protein gene enhances the antitumor effects of radiation via induction of apoptosis - Xiao-Bo Du; Jin-Yi Lang; Jian-Rong XU; You Lu; Yan-Jun Wen; Ju-Mei Zhao; Peng Diao; Zhi-Ping Yuan; Bin Yao; Ling-Yu Fan; Guo-Qing Wang; Li Liu; et al. (Apoptosis, 2008)

Down-regulation of neuropathy target esterase by protein kinase C activation with PMA stimulation - Rui Chen; Ping-An Chang; Ding-Xin Long; Lin Yang; Yi-Jun Wu (Molecular and Cellular Biochemistry, 2007)

Effect of vinasse irrigation on the activity of three enzymes and agronomic characters at seedling stage of sugarcane - Wang Yi-Ding; Mo Yun-Chuan; Wang Wei-Hao; Li Yang-Rui; Ye Yan-Ping (Sugar Tech, 2006)

Ore-forming fluids associated with granite-hosted gold mineralization at the Sanshandao deposit, Jiaodong gold province, China - Hong Rui Fan; Ming Guo Zhai; Yi Han Xie; Jin Hui Yang (Mineralium Deposita, 2003)